Genome-wide SNP data support species boundaries in sympatric Polylepis Ruiz & Pav. (Rosaceae) species from Bolivia and Ecuador - Jay Edneil C. Olivar; Marcus Lehnert; Walter Durka; Stefan Michalski; Christiane M. Ritz; Jana Ebersbach; Alexandra N. Muellner-Riehl; Claudia Segovia-Salcedo; Sofía Acosta-Villamarín; Katya Romoleroux; Erika Priscilla Muriel Mera; Emilio J. Trujillo; et al. (Molecular Phylogenetics and Evolution, 2026)

Pest diversity and their environmental drivers on cashew plantations in Guinea-Bissau - Paola Sierra-Baquero; Sílvia Catarino; Gonçalo J. Costa; Zinha Correia; Maria Rosa Ferreira; Elsa Borges da Silva; Maria Cristina Duarte; Maria M. Romeiras; Edgar Varón-Devia; Luís Catarino; Filipa Monteiro (Agriculture, Ecosystems & Environment, 2026)

Pan-continental assessment of socioeconomic and environmental predictors of PFAS occurrence in European rivers from a harmonised monitoring study - Jun Li; Alistair B.A. Boxall; Caroline Swan; Selwyn Hoeks; Racliffe W.S. Lai; John L. Wilkinson; Recep C. Altinbag; Åsa Arrhenius; Roman Ashauer; Thomas Backhaus; Besnik Baraj; Vasiliki G. Beretsou; et al. (Water Research, 2026)

Pulsed electric fields as a novel strategy to enhance kefir grain biomass growth and kefir beverage production - Graciela A. Miranda-Mejía; Edgar Bottle; Elizabeth Sáenz-García; Gerardo M. Nava; Viridiana Tejada-Ortigoza; Mariana Morales-de la Peña (Innovative Food Science & Emerging Technologies, 2026)

Phase-specific particle size distributions in Hanford tank waste measured by automated SEM–EDS: A statistical comparison across a waste column - Edgar C. Buck; Austin A. Bachman; Jarrod R. Allred; Carolyn A.M. Burns; Amy M. Westesen; Reid A. Peterson (Applied Geochemistry, 2026)

Curiosity meets the Gediz Vallis Ridge: Remnants of a late-stage debris-flow dominated fan in Gale Crater - A.B. Bryk; W.E. Dietrich; K.A. Bennett; V.K. Fox; C.M. Fedo; A.R. Vasavada; A.A. Fraeman; M.P. Lamb; S. Le Mouélic; G. Caravaca; J.M. Davis; J.A. Grant; et al. (Icarus, 2026)

Global invasion dynamics of the charru mussel Mytella strigata (Hanley, 1843): mechanisms, impacts, knowledge gaps, and biosecurity implications - Paravanparambil Rajakumar Jayachandran; Pei-Zhen Ma; Marcel Velásquez; Broc S. Kokesh; Mantodi Jima; Kaent Immanuel N. Uba; César Lodeiros; Naduvilakkandy Vishnudattan; Luiza Costa Mello; Rafael Metri; Pablo Damian Borges Guilherme; Pablo Muniz; et al. (Hydrobiologia, 2026)

Functional venom activity and antivenom neutralization in rattlesnakes across Baja California and Gulf of California islands - Samuel R. Hirst; Edgar Neri-Castro; Emiliano Vázquez-García; Vanessa Zarzosa; Felipe Olvera; Cameron M. VanHorn; Alejandro Alagón; Hector Franz-Chávez; Gamaliel Castañeda-Gaytán; Christopher L. Parkinson; Jason L. Strickland; Miguel Borja; et al. (Toxicon, 2026)

Energy–environmental nexus in green hydrogen-assisted conversion of second-crop canola to sustainable aviation fuel: Toward low-carbon bioenergy systems - Giulia Cruz Lamas; Alexandre Nunes Cardoso; Priscila Seixas Sabaini; Sandra M. Luz; Maria dos Reis Santos Borges; Tainara da S. Costa; Thiago da Silva Gonzales; Marilia Ieda da Silveira Folegatti Matsuura; Bruno Galveas Laviola; Thiago O. Rodrigues; Patrick Rousset; Edgar A. Silveira (Biomass and Bioenergy, 2026)

C-phycocyanin from Arthrospira maxima promotes M2-like/anti-inflammatory phenotype macrophages as a pro-resolving mechanism of inflammation - Z. Mundo-Franco; J. Luna-Herrera; M. Godínez-Victoria; M. Franco-Colín; Vanessa Blas-Valdivia; K. Delgadillo-Gutiérrez; J.C. López-Vázquez; Edgar Cano-Europa (Algal Research, 2026)

Crystal defects drive gold remobilisation in arsenopyrite - Denis Fougerouse; Nicolas Thebaud; David W. Saxey; William D.A. Rickard; Laura Petrella; Siyu Hu; Tommaso Tacchetto; Laure Martin; Wess Edgar; Steven M. Reddy (Geochimica et Cosmochimica Acta, 2026)

Correction: Navigating the winds of change: strategic foresight and the power of weak signals - Jason Jabbour; Debra J Davidson; Henrik Carlsen; Nicholas King; Simone Lucatello; Salvatore Aricò; Fang Lee Cooke; Ranjan Datta; Peter Gluckman; Edgar E. Gutierrez-Espeleta; Andrea Hinwood; Gensuo Jia; et al. (Sustainability Science, 2026)

Navigating the winds of change: strategic foresight and the power of weak signals - Jason Jabbour; Debra J Davidson; Henrik Carlsen; Nicholas King; Simone Lucatello; Salvatore Aricò; Fang Lee Cooke; Ranjan Datta; Peter Gluckman; Edgar E. Gutierrez-Espeleta; Andrea Hinwood; Gensuo Jia; et al. (Sustainability Science, 2026)
In an era of increased complexity, interdependence, uncertainty and rapidly advancing technology, the ability to identify and swiftly adapt to current and future trends is key to progressing sustainability. Intersecting drivers and stressors are converging to destabilize socioecological systems and reshape national, regional and global outlooks. The intersecting and converging crises of the 21st century have exposed the limits of planning that relies too heavily on linear extrapolations from well-known global/mega-trends. This study explores whether a limited number of emerging trends that only manifest as weak signals today serve as central conduits (super-nodes) for amplifying and accelerating systemic disruption. Using an exploratory mixed-methods design, a global Delphi survey ( N = 790, 132 countries) generated 1200 horizon-scan items, inductively coded into 29 clusters. Scenario stress-testing distilled the findings into 280 candidate weak signals—ranked by likelihood, impact, and timing—from which 20 were shortlisted and mapped onto a 20 × 20 influence matrix through structured expert debate. Weighted degree centralities and a 10,000-run bootstrap test identified statistically significant hubs. Results suggest that anticipatory governance can be strengthened by prioritizing high-centrality signals and institutionalizing ongoing weak-signal scanning alongside transparent, multi-source decision-making to avoid cascading risks across planetary-health, economic, and technological systems. At the midpoint of a decade dominated by disruption–climate change, pandemic, geopolitical upheaval, widening inequality, war, misinformation and the rapid rise of Artificial Intelligence–we posit that strategic foresight and informed anticipation is a critical imperative in the pursuit of a global common good and a resilient future.

Bio-based kapok fiber–coconut husk composite aerogel: A sustainable solution for marine oil spill remediation - Ibrahim Ahmed Abass; Makungu M. Madirisha; Elisante E. Mshiu; Sixberth Mlowe; Edgar C. Mapunda (Marine Pollution Bulletin, 2026)

Hydroxypropyl cellulose/thermoplastic polyurethane blend films with reversible optical performance triggered by water - Yimin Yao; Yang Zhou; Glenn A. Spiering; Isabela Trindade Coutinho; Justin M. Anderson; Cameron W. Jordan; Zhenghao Zhai; Cailean Q. Pritchard; Robert B. Moore; Kevin J. Edgar; Michael J. Bortner (Carbohydrate Polymers, 2026)

Microplastic Interaction in the Parasite Infection of Commercial Marine Puffer Fishes (Tetraodontiformes: Tetraodontidae) of the Campeche Coast, Mexico - Ana Luisa May-Tec; Juan Pablo Ek-Huchim; Edgar Fernando Mendoza-Franco; Jaime Navarro-Flores; Jaime Rendón-Von Osten; Merle M. Borges-Ramírez (Acta Parasitologica, 2026)

Industry Development and Diseases in the Norwegian Salmon Aquaculture Industry - Frank Asche; Bård Misund; Tonje Osmundsen; Cecilie S. Walde; Edgar Brun; Mattew DiMaggio; Taryn M. Garlock; Brit Hjeltnes; Marit S. Olsen; Ragnar Tveteras (Reviews in Aquaculture, 2026)
Norwegian salmon aquaculture production has grown rapidly since the 1970s. Accompanying the growing production have been a number of disease challenges of which at least two of the outbreaks threatened the industry's existence. The challenges caused by disease may appear to become more serious as the number of diseases being diagnosed and measures taken by the companies and regulators to manage disease increase. We will review the development of the industry and how diseases have impacted economic viability, the impact of the most important diseases and their control measures as well as the development of the governance and regulatory system in relation to disease. Despite the many disease challenges faced by the industry, we will argue that it has never been in a better position to address these issues and the disease cost per kilo of fish has most likely never been lower. When the industry originated in the 1970s, the knowledge with respect to disease in relation to salmon, such as how to diagnose, prevent or control them, was highly limited. The growth of the industry created a corresponding demand for veterinary knowledge and services, and these have been rapidly growing alongside the industry. This veterinary capacity facilitates the identification of new diseases and the development of novel control measures created with increasing efficiency. However, challenges with diseases will persist, as in all biological production processes, as it is normally not economically optimal to eradicate any disease if this is possible at all.

Wintering Thrushes as Microplastic Pollution Sentinels in the Ground-Foraging Guild of Mediterranean Olive Plantations - Clara Bautista-Romero; José A. Gil-Delgado; Claudia M. Rodríguez-Sierra; Edgar Bernat-Ponce (Water, Air, & Soil Pollution, 2026)

Projected Methane Emissions From a Boreal Thermokarst Bog Are Sensitive to Carbon Substrate Availability, Distribution, and Transport Pathway Dominance - Benjamin C. Maglio; Ruth Rutter; Valeria Briones; Andrew Mullen; Chu‐Chun Chang; Joshua M. Rady; Tobey Carman; Colin Edgar; Eugénie S. Euskirchen; Jennifer D. Watts; Susan M. Natali; Elchin E. Jafarov; et al. (Global Change Biology, 2026)
Methane is a potent greenhouse gas, which traps significantly more heat than carbon dioxide over short timescales, but remains underrepresented in models used for projecting future climate scenarios, particularly in permafrost landscapes. Understanding methane dynamics in northern wetlands is critical for improving projections of high‐latitude carbon feedbacks to the global climate system. To address this, we integrated ecological processes driving methane production, oxidation, and transport pathways into the DVM‐DOS‐TEM terrestrial biosphere model. Using long‐term site observations from a thermokarst bog in boreal Alaska, we calibrated and benchmarked the model against observations of methane and carbon dioxide fluxes, carbon and nitrogen stocks, and soil temperature and moisture. Parameter sensitivity analyses identified opposing correlations for methanogenesis and heterotrophic respiration, revealing a dependence on carbon availability. We also found sensitivity to the distribution of carbon relative to the water table position. Investigation of the dominance of different methane transport pathways demonstrated the need for observations of methane flux partitioning, and the utility in comparing simulated to observed seasonality. The cumulative methane efflux projected to the year 2100 had a range of 211–3470 g C m −2 between low and high warming scenarios. Methane emissions dominated by diffusion showed the greatest variability across projections. Increased soil temperature and carbon availability from permafrost thaw resulted in increasing methane emissions between 2030 and 2060. But methane emission was then limited by a deepening of the water table. Nevertheless, we estimated a positive radiative forcing (i.e., warming) from these mid‐century methane emissions that persisted until 2100. An ebullition‐dominant parameterization led to lower variability but a net negative radiative forcing (i.e., cooling) on average. Our study highlights the importance of representing methane emission pathways and the uncertainty associated with partitioning them on predicting the carbon budget and radiative forcing of wetland ecosystems in high latitudes.

Climate as the Main Driver of Large‐Scale Genetic Patterns and Connectivity in the Expanding Golden Jackal - Alejandro Flores‐Manzanero; Wiesław Bogdanowicz; Milomir Stefanović; Roya Adavoudi; Rasoul Khosravi; Francelly Martínez‐Sosa; Karolina Doan; Yellapu Srinivas; Ovidiu C. Banea; Duško Ćirović; Gianluca D'Amico; Mihajla Djan; et al. (Global Change Biology, 2026)
Rapid global changes in climate and habitats lead to shifts in species' geographic ranges. Range contractions experienced by numerous species may result in local extinctions and connectivity disruptions. In some species, range expansions have been observed instead, suggesting the enlargement of suitable habitats and/or adaptations to changing environments. Despite its importance for wildlife management, our understanding of the factors influencing species' spatial responses to rapidly changing environments remains limited. The golden jackal serves as an excellent model to address this knowledge gap, given its ongoing rapid range expansion. In this study, we investigated environmental factors contributing to genetic connectivity and local adaptation across the expanding range of the golden jackal, based on a comprehensive sampling scheme across Eurasia ( n = 363), a high‐quality set of genomic markers (19,746 SNPs), and a landscape genomics framework. At the continental scale, geographic distance emerged as the predominant factor. At finer spatial scales, genetic connectivity was best explained by climatic predictors, specifically high annual and seasonal variations in precipitation and temperature, which can shape the species' spatial genetic structure by constraining gene flow. Our connectivity models for current and future climatic conditions show that the species' northward expansion is facilitated by changes in these variables in central and northern Europe promoting high connectivity. Precipitation and temperature were also responsible for most local adaptation signals. Given the potential role of hybridization with domestic dogs in shaping range expansion patterns, we investigated the association between environmental conditions and dog admixture proportions. We found no significant trends, indicating a limited effect of dog admixture on habitat choice. Collectively, our findings suggest that the golden jackal has the potential to continue its expansion across Eurasia in response to ongoing global climate change, providing an example of a species that rapidly tracks the expansion of its suitable habitats.

Differential presence of microplastics in the gastrointestinal tract of tropical fish in relation to trophic levels - Merle M. Borges-Ramírez; Rosa E. Martínez-Cerda; Carlos E. Paz-Ríos; Edgar F. Mendoza-Franco; Atahualpa Sosa-López; Jaime Rendón-von Osten (Regional Studies in Marine Science, 2026)

Estuarine structure and connectivity influence seasonal and spatial shifts in the food web structure of fish assemblages - Edgar Abraham Aragón-Flores; Rocío Rodiles-Hernández; Miriam Soria-Barreto; Matteo Cazzanelli; Carmen G. Montaña; María M. Castillo (Regional Studies in Marine Science, 2026)

Calibrating a regional growth and yield model for statewide forest carbon assessment in four common forest types in Minnesota, USA - Matthew B. Russell; John M. Zobel; David C. Wilson; Marcella A. Windmuller-Campione; Tyler S. Gifford; John DuPlissis; Christopher B. Edgar (Forest Policy and Economics, 2026)

Identification of race 2 anthracnose resistance Quantitative Trait Loci using biparental and association panel of diverse watermelon germplasm accessions - Bed Prakash Bhatta; Lakhvir Kaur; Edgar Correa; Gehendra Bhattarai; Takshay Patel; Todd C. Wehner; Kevin M. Crosby; Michael J. Thomson; Subas Malla (Theoretical and Applied Genetics, 2026)

Practical application of BREAM2 in bystander/resident spray drift exposure assessments: accounting for variations in water volume - Kathrin Bürling; Edgars Felkers; Christian J. Kuster; Siân L. Wright-Williams; M. Clare Butler Ellis (Journal of Consumer Protection and Food Safety, 2026)
The EFSA 2022 guidance on non-dietary human exposure, including operators, workers, residents and bystanders, relies on output from the original BREAM model, including simplified extrapolation for different application volumes. This study aims to present the current limitations and challenges in the European Plant Protection Product (PPP) authorizations for non-dietary exposure and risk assessments of residents and bystanders. It also and outlines a concept that could help overcome these limitations while maintaining a health-protective approach. The study demonstrates that refining the value of spray liquid (mL/ person) by more reliably incorporating application volume as a variable in the model leads to a more realistic and scientifically sound risk assessment. This refined approach has been shown to be both reasonable and applicable in the context of PPP registration processes, ahead of its anticipated inclusion in the next EFSA guidance update, where the implementation of BREAM2 is expected.

Drivers of gall rust disease in falcata (Falcataria falcata (L.) Greuter & R.Rankin) plantations across elevation gradients in Mindanao, Philippines - Adrian M. Tulod; Jupiter V. Casas; Mark Jun A. Rojo; Rico A. Marin; Bryan Allan M. Talisay; Eric N. Bruno; Eldon James D. Coraler; Jayson N. Gelaga; Romeo R. Patano; Nympha E. Branzuela; Edgar B. Solis; Sheryl S. Bayang; et al. (Australasian Plant Pathology, 2026)

Implications of alternative biomass and carbon estimation methods for standing dead trees in the United States - Matthew B. Russell; Christopher B. Edgar; Grant M. Domke (Environmental Monitoring and Assessment, 2026)

MODEXMO: A modular non-dietary exposure assessment approach for pesticides using dose-based dermal absorption prediction - Felix M. Kluxen; Korinna Wend; Christiane Wiemann; Edgars Felkers; Neil Morgan (Regulatory Toxicology and Pharmacology, 2026)

Sea urchin herbivory drives subcontinental similarity of tropicalizing reefs - Matthew Rose; Graham J. Edgar; Kate M. Fraser; German A. Soler; Sterling B. Tebbett; Scott D. Ling (Marine Environmental Research, 2026)

Aloysia oblanceolata Moldenke essential oil exhibits antinociceptive activity regulated by opioids, serotonergic, and α2-adrenergic receptors, along with low toxicity and anti-inflammatory effects - Paulo Vinicius L. Santos; Verônica Myrna C. Reis; Edgar T. Chaves; Renata Cunha Silva; Luanna de M. P. Fernandes; Patrícia Danielle Lima de Lima; Joyce Kelly R. da Silva; Pedro Iuri C. da Silva; Pablo Luis B. Figueiredo (Inflammopharmacology, 2025)

Northernmost record of a leucistic Mobula birostris in the Eastern Tropical Pacific - Paul A. Preciado-González; Edgar M. Hoyos-Padilla; Jesús Erick Higuera-Rivas (Marine Biodiversity, 2025)

Sustainable management of post-phytoremediation biomass - Santanu Mukherjee; Alessandra C. Leri; Chathurika Bandaranayaka; Edgar Vázquez-Núñez; Rocío Barros; Aqib Hassan Ali Khan; Pingfan Zhou; Tao Zhang; M. Pilar Bernal; Rafael Clemente; Nanthi Bolan (Energy, Ecology and Environment, 2025)
Organic and inorganic contaminants are entrained into environmental systems through natural and anthropogenic processes, such as mining activities, manufacturing, and waste disposal. In terrestrial and aquatic environments, the contaminant(s) remediation can be achieved by immobilization, thereby inhibiting their dispersal and bioavailability. Mobilization, through leaching and plant uptake, is another process of pollutant removal. Phytoremediation has attracted attention as an eco-friendly alternative for the remediation of contaminated environments. However, the safe management of post-phytoremediation contaminated biomass poses many practical challenges. Understanding the fate of the pollutants in the plants allows the estimation of the possible transfer of the contaminants to the food chain ascertain by-products or residues during biofuel production. Metal-enriched fractions could be used as a valuable source of novel catalysts or reusable materials. The safe conversion of biomass into energy may require sequestering contaminants at any step of the process, preferably upstream of the energy conversion or as a pre-treatment of plant biomass. Through gasification or pyrolysis of post-remediation biomass, bioenergy products (including syngas, oil, hydrogen gas, biochar, and hydrochar) can be used for heating and electricity generation. A comparative evaluation among pyrolysis, gasification, combustion, and liquefaction/fermentation processes for biofuel production from post-phytoremediation biomass suggests that pyrolysis is the strategy with the lowest transfer of toxic metals to the final products. This review presents critical discussions of the processes involved in phytoremediation of contaminated environments, the redistribution of contaminants within plant biomass, the sustainable management of post-phytoremediation biomass, and the unintended environmental consequences of phytoremediation.

Linking Climate and Demography to Predict Population Dynamics and Persistence Under Global Change - Jennifer L. Williams; Amy L. Angert; Aldo Compagnoni; Ali Campbell; Megan L. DeMarche; Margaret E. K. Evans; Joshua C. Fowler; Edgar J. González; Amy M. Iler; Jenna A. Loesberg; Allison M. Louthan; Alexandra B. Martin; et al. (Ecology Letters, 2025)
Predicting the effects of climate change on plant and animal populations is an urgent challenge for understanding the fate of biodiversity under global change. At the surface, quantifying how climate drives the vital rates that underlie population dynamics appears simple, yet many decisions are required to connect climate to demographic data. Competing approaches have emerged in the literature with little consensus around best practices. Here we provide a practical guide for how to best link vital rates to climate for the purposes of inference and projection of population dynamics. We first describe the sources of demographic and climate data underlying population models. We then focus on best practices to model the relationships between vital rates and climate, highlighting what we can learn from mechanistic and phenomenological models. Finally, we discuss the challenges of prediction and forecasting in the face of uncertainty about climate‐demographic relationships as well as future climate. We conclude by suggesting ways forward to build this field of research into one that makes robust forecasts of population persistence, with opportunities for synthesis across species.

Sustainable agriculture with cyanobacterial biomass: Soil experiments on spinach and radish plants - Anabella Massa; Diogo Martins; Joana Azevedo; Ana I. Prieto; Ana M. Camean; Leticia Diez-Quijada; Angeles Jos; Mariana Reimão; Rui Azevedo; Edgar Pinto; Agostinho Almeida; Vitor Vasconcelos; et al. (Science of The Total Environment, 2025)

Potential nursery area for the endangered oceanic manta ray in the Gulf of California, México - Paul A. Preciado-González; Felipe Galván-Magaña; James T. Ketchum; Héctor Villalobos-Ortiz; Rogelio González-Armas; Jesús Erick Higuera-Rivas; Arturo Ayala-Bocos; Paola Ruffo-Ruffo; Georgina Saad-Navarro; Edgar M. Hoyos-Padilla (Environmental Biology of Fishes, 2025)

Tertiary water treatment with Sargassum spp Filter: Pollutant hydraulic loss coefficient and removal capacity - Dafne García-Trejo; Jorge A. Segura Meza; Sandra L. Rosales-Silvestre; Omar E. Cabrera-Lumbreras; Faustino De Luna-Cruz; Víctor M. Ortiz-Martínez; Maritza Liliana Arganis-Juárez; Margarita E. Preciado; José L. López-Miranda; Valeria Chávez; Edgar Mendoza; Miriam Estévez-González; et al. (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Microalgae-based biorefinery for schnapps vinasse treatment: biomass production, nutrient recovery and carbohydrates, proteins and lipids accumulation - Marco Alberto Mamani Condori; Jhenily Isabella Contreras Beltran; Maria Irene Larico Flores; Esthefany Mollo Torres; Nemesio Edgar Veliz Llayqui; José C. M. Pires (Journal of Applied Phycology, 2025)

Reactant-dependent stability of supported metal catalysts for hydrogen storage in N-heterocyclic carriers - Sara Ahsan; Matthew D. Edgar; Sirinada Chanthachaiwat; Jingrui Wei; Paul M. Voyles; Siddarth H. Krishna (Chemical Engineering Journal, 2025)

Global change drivers alter weed performance and threaten forage production in an Andean agroecosystem - Anna M. Visscher; Steven Vanek; Jhon Huaraca; Jamelith Mendoza; Raul Ccanto; Katherin Meza; Edgar Olivera; Steven J. Fonte (Agriculture, Ecosystems & Environment, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Fault interactions and subsurface deformation in the Mexicali Valley: Implications for seismic hazard assessment at the México-USA border - Cristian A. Gallegos-Castillo; Mario González-Escobar; Jaime A. Reyes-López; Joann M. Stock; Sergio M. Arregui-Ojeda; Carlos Simón Reyes-Martínez; Edgar A. Mastache-Román (Tectonophysics, 2025)

Primate teeth are good proxies for understanding past water inputs and seasonality - Tanya M. Smith; Janaína N. Ávila; Jelmer W. Eerkens; Daniel R. Green; Katie Hinde; Edgar Huerta; Paul Tafforeau; Ian S. Williams (Geochimica et Cosmochimica Acta, 2025)

Traditional and industrial approaches to oil palm cultivation alter the biodiversity of ground-dwelling arthropods in Liberia (West Africa) - Jonathan H. Timperley; Brogan L. Pett; Bility Geninyan; Ari Saputra; Abraham Vincent; Romeo Weah; Benedictus Freeman; Marshall Guahn; Peter M. Hadfield; Morris T. Jah; Tiecanna Jones; Rudy H. Widodo; et al. (Agriculture, Ecosystems & Environment, 2025)

Effects of apples ( Malus domestica ) and their derivatives on metabolic conditions related to inflammation and oxidative stress and an overview of by-products use in food processing - Otávio Simões Girotto; Otávio Oliveira Furlan; Renato Cesar Moretti Junior; Ricardo de Alvares Goulart; Edgar Baldi Junior; Caroline Barbalho-Lamas; Lucas Fornari Laurindo; Sandra M. Barbalho (Critical Reviews in Food Science and Nutrition, 2025)

Consistent Unimodal Body Length Distributions in Hundreds of Reef Fishes Across Diverse Life Histories - Freddie J. Heather; Shane A. Richards; Nils C. Krueck; Rick D. Stuart‐Smith; Simon J. Brandl; Jordan M. Casey; Graham J. Edgar; Neville Barrett; Valeriano Parravicini; Asta Audzijonyte (Fish and Fisheries, 2025)
Animal body size distributions result from interactions of growth, mortality and recruitment. In ecology and fisheries science, theoretical models of fish body size distributions are widely used but rely on life‐history parameters—growth coefficient (K) and natural mortality rate (M)—that remain unknown for most species and are challenging to estimate. Analysing data from underwater visual surveys and exhaustive sampling, representing 3068 populations across 797 species of shallow‐water, mostly unfished marine fishes, we demonstrate that post‐recruitment body length distributions exhibit a consistent unimodal shape across species and populations. When scaled to the mean body length, these distributions are strikingly similar across all teleost and elasmobranch species, with diverse life histories and maximum body sizes ranging from 1 cm to 3 m. Observed size structure can be approximated by a truncated normal distribution with a coefficient of variation of ~0.34 (SE = 0.002). Such consistent observed body size distributions could be aligned with Beverton–Holt population dynamics theory, if assuming an M/K ratio of ~1.5 and logistic observational selectivity with 50% detectability at ~40% of maximum body length. Alternatively, observed distributions could reflect deviations from theoretical expectations, and reconciling the unimodal distributions with theory may require relaxing some model assumptions, such as continuous recruitment, constant density‐independent growth or constant natural mortality. Overall, the consistency of population‐ and species‐level body length distributions means that unfished size structure could be predicted from a single body size parameter. It also suggests evolutionary convergence of diverse growth and mortality processes towards a narrow range of viable outcomes.

Determining the relative scientific and cultural “value” of the UK's in-situ dinosaur track sites - Kirsty M. Edgar; Richard J. Butler; Jonathan G. Larwood; Joshua J.P. Smith (Proceedings of the Geologists' Association, 2025)

Temperature matters: Acute and latent toxicity of diluted bitumen to developing salmon is potentiated by a modest increase in water temperature - Derin M. Çalık; Feng Lin; Mackenzie Edgar; Anthony P. Farrell; Christopher J. Kennedy; Todd E. Gillis; Sarah L. Alderman (Aquatic Toxicology, 2025)

Imaging of Intracranial Aneurysms: A Review of Standard and Advanced Imaging Techniques - Sricharan S. Veeturi; Samuel Hall; Soichiro Fujimura; Mahmud Mossa-Basha; Elena Sagues; Edgar A. Samaniego; Vincent M. Tutino (Translational Stroke Research, 2025)

Depth-Specific Hypoxic Responses to Spreading Depolarizations in Gyrencephalic Swine Cortex Unveiled by Photoacoustic Imaging - Edgar Santos; Juan M. Lopez-Navarro; Marcos Alejandro Suarez-Gutierrez; Niklas Holzwarth; Pablo Albiña-Palmarola; Thomas Kirchner; Adrian Hernandez-Aguilera; Jose Antonio Fernandez-Amador; Farzam Vazifehdan; Johannes Woitzik; Lena Maier-Hein; Renan Sanchez-Porras (Translational Stroke Research, 2025)

Trophic Interactions Are Key to Understanding the Effects of Global Change on the Distribution and Functional Role of the Brown Bear - Pablo M. Lucas; Wilfried Thuiller; Lauren Talluto; Ester Polaina; Jörg Albrecht; Nuria Selva; Marta De Barba; Vincenzo Penteriani; Maya Guéguen; Niko Balkenhol; Trishna Dutta; Ancuta Fedorca; et al. (Global Change Biology, 2025)
Biotic interactions are expected to influence species' responses to global changes, but they are rarely considered across broad spatial extents. Abiotic factors are thought to operate at larger spatial scales, while biotic factors, such as species interactions, are considered more important at local scales within communities, in part because of the knowledge gap on species interactions at large spatial scales (i.e., the Eltonian shortfall). We assessed, at a continental scale, (i) the importance of biotic interactions, through food webs, on species distributions, and (ii) how biotic interactions under scenarios of climate and land‐use change may affect the distribution of the brown bear ( Ursus arctos ). We built a highly detailed, spatially dynamic, and empirically sampled food web based on the energy contribution of 276 brown bear food species from different taxa (plants, vertebrates, and invertebrates) and their ensemble habitat models at high resolution across Europe. Then, combining energy contribution and predicted habitat of food species, we modelled energy contribution across space and included these layers within Bayesian‐based models of the brown bear distribution in Europe. The inclusion of biotic interactions considerably improved our understanding of brown bear distribution at large (continental) scales compared with Bayesian models including only abiotic factors (climate and land use). Predicted future range shifts, which included changes in the distribution of food species, varied greatly when considering various scenarios of change in biotic factors, providing a warning that future indirect climate and land‐use change are likely to have strong but highly uncertain impacts on species biogeography. Our study confirmed that advancing our understanding of ecological networks of species interactions will improve future projections of biodiversity change, especially for modelling species distributions and their functional role under climate and land‐use change scenarios, which is key for effective conservation of biodiversity and ecosystem services.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Pediment formation and subsequent erosion in Gale crater: Clues to the climate history of Mars - A.B. Bryk; W.E. Dietrich; K.A. Bennett; V.K. Fox; C.M. Fedo; M.P. Lamb; E.S. Kite; L.M. Thompson; S.G. Banham; J. Schieber; J.A. Grant; A.R. Vasavada; et al. (Icarus, 2025)

Correction to: Insular and mainland interconnectivity in the movements of oceanic manta rays (Mobula birostris) off Mexico in the Eastern Tropical Pacific - Robert D. Rubin; Katherine R. Kumli; A. Peter Klimley; Joshua D. Stewart; James T. Ketchum; Edgar M. Hoyos‑Padilla; Felipe Galván‑Magaña; Aldo A. Zavala‑Jiménez; Iliana A. Fonseca‑Ponce; Megan Saunders; P. Santiago Dominguez‑Sanchez; Paul Ahuja; et al. (Environmental Biology of Fishes, 2025)

Insular and mainland interconnectivity in the movements of oceanic manta rays (Mobula birostris) off Mexico in the Eastern Tropical Pacific - Robert D. Rubin; Katherine R. Kumli; A. Peter Klimley; Joshua D. Stewart; James T. Ketchum; Edgar M. Hoyos-Padilla; Felipe Galván-Magaña; Aldo A. Zavala-Jiménez; Iliana A. Fonseca-Ponce; Megan Saunders; P. Santiago Dominguez-Sanchez; Paul Ahuja; et al. (Environmental Biology of Fishes, 2025)

Basin Style Variation Along a Transform Fault: Southern Colorado River Delta, Baja California, México - Mario González-Escobar; Carlos Simón Reyes-Martínez; Cristian A. Gallegos-Castillo; Sergio M. Arregui-Ojeda; Edgar A. Mastache-Román (Pure and Applied Geophysics, 2025)

Effect of torrefaction severity on the energy recovery from amazonian wood residues for decentralized energy conversion systems - Edgar A. Silveira; Giulia Cruz Lamas; Pedro Paulo de O. Rodrigues; Normando P.B. Souto; Bruno Sant’Anna Chaves; Luiz Gustavo Oliveira Galvão; Lucélia A. Macedo; Juliana Sabino Rodrigues; Sandra M. Luz; Patrick Rousset; Thiago de Paula Protásio (Biomass and Bioenergy, 2025)

Editorial: Proceedings from the 16th International Conference on Subarachnoid Hemorrhage (iSAH) Meeting - Redi Rahmani; Mahmud Mossa-Basha; Vincent M. Tutino; Edgar A. Samaniego; Devin W. McBride (Translational Stroke Research, 2025)

Radiomics-Based Predictive Nomogram for Assessing the Risk of Intracranial Aneurysms - Sricharan S. Veeturi; Arshaq Saleem; Diego J. Ojeda; Elena Sagues; Sebastian Sanchez; Andres Gudino; Elad I. Levy; David Hasan; Adnan H. Siddiqui; Vincent M. Tutino; Edgar A. Samaniego (Translational Stroke Research, 2025)

Energy and exergy analysis of a two-stage cascade vapor compression refrigeration system with modified system configuration - Dave Nygeil G. Patiluna; Edgar Alan A. Donasco; Noel M. Hernandez; Junil Bien A. Mamalias; Rommel R. Viña (International Journal of Refrigeration, 2025)

Evaluation of the potential of annatto seed powder to reduce the formation of heterocyclic amines in charcoal-grilled and pan-fried beef patties - Thaís de Moura Neves-Gonçalves; Edgar Pinto; Olga Viegas; Anna Rafaela Cavalcante Braga; Leonardo M. de Souza Mesquita; Isabel Maria Pinto Leite Viegas Oliveira Ferreira; Carmen García-Jares; Veridiana Vera De Rosso; Semíramis Martins Álvares Domene (Food Chemistry, 2025)

Retraction notice to “Toxicity of spike fragments SARS-CoV-2 S protein for zebrafish: A tool to study its hazardous for human health?” [Sci. Total Environ. 813 (2022) / 152345] - Bianca H. Ventura Fernandes; Natália Martins Feitosa; Ana Paula Barbosa; Camila Gasque Bomfim; Anali M.B. Garnique; Ivana F. Rosa; Maira S. Rodrigues; Lucas B. Doretto; Daniel F. Costa; Bruno Camargo-dos-Santos; Gabrielli A. Franco; João Favero Neto; et al. (Science of The Total Environment, 2024)

Data collection initiatives of the crop protection industry – A mission to improve non-dietary risk assessment in Europe - Neil Morgan; Sarah Adham; Edgars Felkers; Felix M. Kluxen; Christian J. Kuster; Christiane Wiemann (Regulatory Toxicology and Pharmacology, 2024)

Dietary supplementation of mineral nanoparticles for channel catfish (Ictalurus punctatus) - Vitor F. Silva; José Luiz P. Mouriño; Maurício L. Martins; Pedro L. P. F. Carvalho; Edgar D. Rodrigues; Delbert M. Gatlin; Matt J. Griffin; Caitlin E. Older; Fernando Y. Yamamoto (Fish Physiology and Biochemistry, 2024)

Phylogeny, pathogenicity, and fungicide sensitivity of Botryosphaeriaceae fungi associated with Persian lime dieback in Sinaloa, Mexico - Perla R. Núñez-García; José A. Carrillo-Fasio; Kamila C. Correia; Edgar H. Nieto-López; Guadalupe A. Mora-Romero; José B. Valdéz-Torres; Carlos A. López-Orona; Juan M. Tovar-Pedraza (Physiological and Molecular Plant Pathology, 2024)

Monitoring drift and associated biodiversity of nearshore rafts of holopelagic Sargassum spp. in the Mexican Caribbean - Brigitta I. van Tussenbroek; L. Verónica Monroy-Velázquez; Dení Rodríguez; L. Parmenio Suescún-Bolívar; Patricia E. Thomé; Daniel Cerqueda-García; José Q. García-Maldonado; Isis G. Martínez-López; José Antonio López-Portillo; M. Guadalupe Barba-Santos; Miguel Angel Gómez-Reali; J. Edgar Escalante-Mancera (Aquatic Botany, 2024)

A new Neu—a syngeneic model of spontaneously metastatic HER2-positive breast cancer - Aaron G. Baugh; Edgar Gonzalez; Valerie H. Narumi; Jesse Kreger; Yingtong Liu; Christine Rafie; Sofi Castanon; Julie Jang; Luciane T. Kagohara; Dimitra P. Anastasiadou; James Leatherman; Todd Armstrong; et al. (Clinical & Experimental Metastasis, 2024)
Metastatic disease results from the dissemination of tumor cells beyond their organ of origin to grow in distant organs and is the primary cause of death in patients with advanced breast cancer. Preclinical murine models in which primary tumors spontaneously metastasize are valuable tools for studying metastatic progression and novel cancer treatment combinations. Here, we characterize a novel syngeneic murine breast tumor cell line that provides a model of spontaneously metastatic neu-expressing breast cancer with quicker onset of widespread metastases after orthotopic mammary implantation in immune-competent NeuN mice. The NT2.5-lung metastasis (-LM) cell line was derived from serial passaging of tumor cells that were macro-dissected from spontaneous lung metastases after orthotopic mammary implantation of parental NT2.5 cells. Within one week of NT2.5-LM implantation, metastases are observed in the lungs. Within four weeks, metastases are also observed in the bones, spleen, colon, and liver. We demonstrate that NT2.5-LM metastases are positive for NeuN—the murine equivalent of human epidermal growth factor 2 (HER2). We further demonstrate altered expression of markers of epithelial-to-mesenchymal transition (EMT), suggestive of their enhanced metastatic potential. Genomic analyses support these findings and reveal enrichment in EMT-regulating pathways. In addition, the metastases are rapidly growing, proliferative, and responsive to HER2-directed therapy. The new NT2.5-LM model provides certain advantages over the parental NT2/NT2.5 model, given its more rapid and spontaneous development of metastases. Besides investigating mechanisms of metastatic progression, this new model may be used for the rationalized development of novel therapeutic interventions and assessment of therapeutic responses.

Conversion of rainforest to both traditional and industrial oil palm systems changes the biodiversity, web-building, and prey capture of understory spiders (Liberia, West Africa) - Michael D. Pashkevich; Brogan L. Pett; Cicely A.M. Marshall; Jean-Pierre Caliman; Benedictus Freeman; Marshall M. Guahn; Peter M. Hadfield; Matthew T. Hendren; Morris T. Jah; Tiecanna Jones; Ari Saputra; Rudy H. Widodo; et al. (Agriculture, Ecosystems & Environment, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Anti-oomycete activity and plant growth promoting properties of avocado fungal endophytes - Emma I. Nieves-Campos; Alejandro Méndez-Bravo; Yareli Pérez-Bautista; Jesús Llanderal-Mendoza; Edgar Guevara-Avendaño; Itzel A. Solís-García; Nayeli A. Diyarza-Sandoval; Silvia M. Contreras-Ramos; Jacobo Rodriguez-Campos; Alfonso Méndez-Bravo; Frédérique Reverchon (Rhizosphere, 2024)

Waste-to-energy in the civil-construction sector toward the valuation of wood construction residues: Integration of torrefaction process - Thais Barbosa; Bruno Sant’Anna Chaves; Luiz Gustavo O. Galvão; Giulia Cruz Lamas; Pedro Paulo de Oliveira Rodrigues; Mayara Gabi Moreira; Thiago de Paula Protásio; Sandra M. Luz; Juliana Sabino Rodrigues; Edgar A. Silveira (Fuel, 2024)

An eco-friendly approach for analysing sugars, minerals, and colour in brown sugar using digital image processing and machine learning - Vandressa Alves; Jeferson M. dos Santos; Olga Viegas; Edgar Pinto; Isabel M.P.L.V.O. Ferreira; Vanderlei Aparecido Lima; Maria L. Felsner (Food Research International, 2024)

Unleashing the Potential of the 360° Baited Remote Underwater Video System (BRUVS): An Innovative Design for Complex Habitats - Marisa A. Gomes; Catarina M. Alves; Fábio Faria; Regina Neto; Edgar Fernandes; Jesus S. Troncoso; Pedro T. Gomes (Journal of Marine Science and Engineering, 2024)
Coastal ecosystems are vital for numerous demersal and benthopelagic species, offering critical habitats throughout their life cycles. Effective monitoring of these species in complex coastal environments is essential, yet traditional survey methodologies are often impractical due to environmental constraints like strong currents and high wave regimes. This study introduces a new cost-effective Baited Remote Underwater Video System (BRUVS) design featuring a vertical structure and 360° cameras developed to overcome limitations of traditional BRUVS, such as system anchoring, overturning, and restricted frame view. The new design was compared against a previous one used on the northwest Iberian coast. Key performance metrics included species detection, habitat identification, and operational efficiency under complex hydrodynamic conditions. Findings reveal that the two designs can effectively identify the common species typically observed in the study area. However, the new design outperformed the previous by significantly reducing equipment losses and anchoring issues. This enhancement in field operations’ simplicity, operability, portability, and resiliency underscores the new system’s potential as a cost-effective and efficient tool for demersal and benthopelagic ecological surveys in challenging coastal seascapes. This innovative BRUVS design offers advanced monitoring solutions, improving habitat assessment accuracy and responsiveness.

Thirteen new species of Urucumania (Phasmatodea: Pseudophasmatidae) stick insects from Brazil and Bolivia - Victor M. Ghirotto; Edgar B. Crispino; Phillip W. Engelking; Pedro Alvaro Barbosa Aguiar Neves; Pablo Valero; Thiago Ferreira Soares; Thiago Silva-Soares; Thiago José De Souza Alves; Pedro Sisnando; Raphael A. Heleodoro; Oskar Conle; Frank Hennemann; et al. (Biologia, 2024)

Automated SEM analysis of particles in Hanford tank waste - Jarrod R. Allred; Edgar C. Buck; Richard C. Daniel; John G.H. Geeting; Amy M. Westesen; Reid A. Peterson (Journal of Hazardous Materials, 2024)

Fangs and foliage: Unearthing the haemotoxic secrets of cannabis-dwelling rattlesnakes - Lachlan A. Bourke; Christina N. Zdenek; Tam M. Huynh; Wayne C. Hodgson; Alejandro Alagón; Edgar N. Castro; Jason Jones; Bryan G. Fry (Toxicon, 2024)

Proposals for new spray drift exposure values in orchards and vineyards for residents and bystanders - Udo Blaschke; Edgars Felkers; Nicola J. Hewitt; Felix M. Kluxen; Neil Morgan; Christiane Wiemann (Regulatory Toxicology and Pharmacology, 2024)

Proposals for new transfer coefficient (TC) values for worker re-entry activities in grape vineyards - Udo Blaschke; Edgars Felkers; Nicola J. Hewitt; Felix M. Kluxen; Neil Morgan; Christiane Wiemann (Regulatory Toxicology and Pharmacology, 2024)

Predicting total biogas potential of food waste using the initial output of biogas potential tests as input data to train an artificial neural network - Sarah M. Hunter; Edgar Blanco; Adiuan Borrion (Bioresource Technology Reports, 2024)

Dynamic Effects of a Regulating Valve in the Assessment of Water Leakages in Single Pipelines - Oscar E. Coronado-Hernández; Modesto Pérez-Sánchez; Alfonso Arrieta-Pastrana; Vicente S. Fuertes-Miquel; Jairo R. Coronado-Hernández; Edgar Quiñones-Bolaños; Helena M. Ramos (Water Resources Management, 2024)
Water losses in water distribution systems are typically analysed using extended period simulations, where its numerical resolution is commonly achieved using the gradient method. These models assume that adjustments to regulating valves occur, either manually or automatically, over an extended period of time, then the system inertia can be neglected. This research introduces the development of a rigid water column model for analysing water leakages in single pipelines, which can be employed to account for regulation valve adjustments in shorter time periods, thereby providing greater accuracy when assessing water losses. The application to a case study is presented to analyse pressure variations and leakage flow patterns over 30, 60, and 180 s. A comparison between the extended period simulation and rigid water column model is presented in order to note the order of magnitude on leakages when the system inertia is not considered. The results confirm that is crucial for water utilities the consideration of inertial system to simulate adequately opening and closure manoeuvres in water distribution systems, since according to the case study the extended period simulation can overestimated or underestimated the total leakage volume in percentages of 37.1 and 55.2 $$%$$ % , respectively.

Long-term data in agricultural landscapes indicate that insect decline promotes pests well adapted to environmental changes - Tim M. Ziesche; Frank Ordon; Edgar Schliephake; Torsten Will (Journal of Pest Science, 2024)
Increasing evidence suggests that land-use intensification contributes to destabilization of trophic networks of insect communities in agriculture resulting in a loss of biodiversity. However, a more detailed understanding of the causes and consequences of the widely reported insect decline is still lacking. Here, we used standardised daily long-term data on the activity of flying insects (~ 250 d/year) to describe the interactive effects of climate warming in intensively cultivated regions and changes in predatory taxa on the general long-term trend of insects and the regulation of herbivores. While the intensely managed landscapes examined in this study show a substantial decline in several taxonomic groups (95.1% total biomass loss in 24 year), the data on aphids support a general assumption that biodiversity loss is often closely associated with arising pest problems. Aphids being pests in agroecosystems develop earlier in spring in overall higher annual abundances. The data highlight that regional insect abundances have declined over recent decades in agricultural landscapes, thus indicating fundamental effects on food webs and insect herbivore performance.

Efficiency of working coveralls and chemical resistant gloves in reducing operator exposure to pesticides - Christian J. Kuster; Felix M. Kluxen; Edgars Felkers; Neil Morgan; Nicola J. Hewitt; Julien Durand-Reville (Journal of Consumer Protection and Food Safety, 2024)
Personal Protective Equipment (PPE) is used to reduce exposure when working with chemicals. For pesticides, exposure scenarios comprise mixing and loading (M&L) and application. The exposure prediction model recommended by European regulatory agencies for operator risk assessments—the Agricultural Operator Exposure Model (AOEM) – is based on 48 operator exposure studies involving over 500 professional operators from 10 European countries in typical working situations to assess exposure under realistic field conditions. We used the AOEM data to assess the efficiency of exposure reduction resulting from wearing chemical-resistant nitrile gloves and non-certified working coveralls during M&L (tank and backpack sprayer), applications using groundboom and airblast spraying, and outdoor and indoor (greenhouse) applications using handheld sprayers. All studies indicated consistent and high exposure reduction > 90% for gloves and non-certified coveralls across all investigated scenarios. Exceptions were almost exclusively observed when an operator incorrectly used the PPE. The mean exposure reduction from all operators, including those that used PPE incorrectly, was 95.0% for gloves and 96.4% for polyester/cotton working coveralls during M&L, and 91.1% for gloves and 94.9% for non-certified coveralls during all application scenarios. This analysis confirms the essential role of PPE and non-certified working coveralls in reducing operator exposure to pesticides. Outliers indicate that operators need to be properly trained and adhere to label instructions to apply pesticides according to good agricultural practices.

The socioecological benefits and consequences of oil palm cultivation in its native range: The Sustainable Oil Palm in West Africa (SOPWA) Project - Michael D. Pashkevich; Cicely A.M. Marshall; Benedictus Freeman; Valentine J. Reiss-Woolever; Jean-Pierre Caliman; Julia Drewer; Becky Heath; Matthew T. Hendren; Ari Saputra; Jake Stone; Jonathan H. Timperley; William Draper; et al. (Science of The Total Environment, 2024)

Overcome imposter syndrome: Contribute to working groups and build strong networks - Amanda E. Bates; Megan A. Davies; Rick D. Stuart-Smith; Natali Lazzari; Jonathan S. Lefcheck; Scott D. Ling; Camille Mellin; David Mouillot; Anthony T.F. Bernard; Scott Bennett; Christopher J. Brown; Michael T. Burrows; et al. (Biological Conservation, 2024)

Incorporating climate-readiness into fisheries management strategies - Elizabeth Talbot; Jean-Beth S. Jontila; Benjamin J. Gonzales; Roger G. Dolorosa; Edgar D. Jose; Recca Sajorne; Sevrine Sailley; Susan Kay; Ana M. Queirós (Science of The Total Environment, 2024)

Amplification of the antioxidant properties of myricetin, fisetin, and morin following their oxidation - M. Fernanda Arias-Santé; Jocelyn Fuentes; Camila Ojeda; Mario Aranda; Edgar Pastene; Hernán Speisky (Food Chemistry, 2024)

Traditional soil fertility management ameliorates climate change impacts on traditional Andean crops within smallholder farming systems - Anna M. Visscher; Steven Vanek; Jhon Huaraca; Jamelith Mendoza; Raul Ccanto; Katherin Meza; Edgar Olivera; Maria Scurrah; Camilla Wellstein; Gianmaria Bonari; Stefan Zerbe; Steven J. Fonte (Science of The Total Environment, 2024)

On the role of methyl groups in the molecular architectures of mesophase pitches - Aparna Annamraju; Gang Seob Jung; Samarthya Bhagia; Joshua T. Damron; Matthew R. Ryder; Mark A. Arnould; Ercan Cakmak; Frederic Vautard; Ryan M. Paul; Stephan Irle; Nidia C. Gallego; Edgar Lara Curzio (Fuel, 2024)

Range-wide phylogeography of the golden jackals (Canis aureus) reveals multiple sources of recent spatial expansion and admixture with dogs at the expansion front - Milomir Stefanović; Wiesław Bogdanowicz; Roya Adavoudi; Francelly Martínez-Sosa; Karolina Doan; Alejandro Flores-Manzanero; Yellapu Srinivas; Ovidiu C. Banea; Duško Ćirović; Gianluca D'Amico; Mihajla Djan; Giorgos Giannatos; et al. (Biological Conservation, 2024)

A comparison between field measurements of vapour concentrations of plant protection products and predictions by the BROWSE model - M. Clare Butler Ellis; Edgars Felkers; Sarah Adham; Anne-Kim Vinck; Kathrin Bürling; Neil Morgan (Regulatory Toxicology and Pharmacology, 2023)

Low frequency of resistance to thiophanate-methyl in Monilinia fructicola populations from southeastern United States peach orchards - William P. Gura; Jhulia Gelain; Edward J. Sikora; Edgar L. Vinson; Phillip M. Brannen; Guido Schnabel (Pesticide Biochemistry and Physiology, 2023)

Bioavailability of bioactive compounds in Hibiscus sabdariffa beverage as a potential anti-inflammatory - Alejandro Arce-Reynoso; Raquel Mateos; Edgar J. Mendivil; Víctor M. Zamora-Gasga; S.G. Sáyago-Ayerdi (Food Research International, 2023)

Tracking 20 years of forest demographics in east Texas, USA, using national forest inventory data - Paul A. Klockow; Christopher B. Edgar; Grant M. Domke; Christopher W. Woodall; Matthew B. Russell (Environmental Monitoring and Assessment, 2023)

Vibrational entropy of disordering in omphacite - Artur Benisek; Edgar Dachs; Michael A. Carpenter; Bastian Joachim-Mrosko; Noreen M. Vielreicher; Manfred Wildner (Physics and Chemistry of Minerals, 2023)
The cations of an ordered omphacite from the Tauern window were gradually disordered in piston cylinder experiments at temperatures between 850 and 1150 °C. The samples were examined by X-ray powder diffraction and then investigated using low-temperature calorimetry and IR spectroscopy. The low-temperature heat capacity data were used to obtain the vibrational entropies, and the line broadening of the IR spectra served as a tool to investigate the disordering enthalpy. These data were then used to calculate the configurational entropy as a function of temperature. The vibrational entropy does not change during the cation ordering phase transition from space group C2/c to P2/n at 865 °C but increases with a further temperature increase due to the reduction of short-range order.

Why are you hitting yourself? Whole-exome sequencing diagnosis of monogenic autoimmunity - Lina M. Castano-Jaramillo; Francisco Rivas Larrauri; Selma C. Scheffler-Mendoza; Alonso Gutierrez-Hernandez; Juan Carlos Bustamante Ogando; Paulina Colin; Margarita Ortega Cisneros; Sandra Rajme-López; Edgar Alejandro Medina-Torres; Laura Berron Ruiz; Ana Luisa Rodriguez-Lozano; Sara Elva Espinosa Padilla; et al. (Journal of Genetics, 2023)

Overview of the tectonic and seismicity in Continental Borderland (offshore) Baja California, México - Mario González Escobar; Cristian A. Gallegos-Castillo; Sergio M. Arregui-Ojeda; Edgar A. Mastache-Román; Carlos S. Reyes-Martínez; Young Ho Aladro-Chio (Journal of South American Earth Sciences, 2023)

Fermentative parameters and chemical composition of mixed silages from corn-crotalaria intercropping - Carolina M. Costa Araujo; Edgar S. Jara Galeano; Marco A.P. Orrico Junior; Tatiane Fernandes; Joyce P. Alves; Marciana Retore; Mabio S.J. Silva; Ana C.A. Orrico; Rodrigo A. Garcia; Luis A.Z. Machado (Animal Feed Science and Technology, 2023)

Morphological Performance of Vegetated and Non-Vegetated Coastal Dunes with Rocky and Geotextile Tube Cores under Storm Conditions - Carmelo Maximiliano-Cordova; Rodolfo Silva; Edgar Mendoza; Valeria Chávez; M. Luisa Martínez; Rusty A. Feagin (Journal of Marine Science and Engineering, 2023)
Coastal dune restoration projects are increasingly seen as a means of protecting the coast against storms, especially with the use of natural (plants), artificial (geotextile tube cores) and hybrid (plants and geotextile tube) elements. As geotextile tube cores have been found to negatively affect dune and beach natural morphodynamics, rocky cores are thus seen as a potential alternative. We carried out laboratory experiments to compare the performance of dunes with rocky cores, geotextile cores, and both types when coupled with planted vegetation. We investigated these elements in the context of scaled mild, moderate, and intense storm conditions. The results showed that dunes with either type of core lost more sand than dunes without cores. The addition of plants generally reduced the erosion across the various options, but most strongly for rocky cores under mild and moderate storm conditions. We also found that dunes with a high density of plants were best for intense conditions. Overall, the use of rocky dune cores, when coupled with plants, is the most suitable and sustainable alternative option in hybrid engineering projects.

Analysis of truncated growth hormone receptor 1 in the differential growth of fine flounder Paralichthys adspersus - Alan Marín; Andrés M. Alonso; Tomás H. Delgadin; Edgar A. López-Landavery; Lise Jara Cometivos; Anaid Saavedra-Flores; Lorenzo E. Reyes-Flores; Carmen G. Yzásiga-Barrera; Juan I. Fernandino; Eliana Zelada-Mázmela (Aquaculture, 2023)

A techno-economic assessment of sCO2 Brayton cycles for low-grade geothermal reservoirs - Eduardo Ruiz-Casanova; Carlos Rubio-Maya; J. Jesús Pacheco-Ibarra; Víctor M. Ambriz-Díaz; C.J. Torres Pacheco; Edgar Pastor-Martínez (Geothermics, 2023)

Multi-stemming enhances tree survival and growth in Borneo’s logged forests - Jakub Kvasnica; Radim Matula; Martin Rejžek; Robert M. Ewers; Terhi Riutta; Edgar C. Turner; Reuben Nilus; Martin Svátek (Forest Ecology and Management, 2023)

Practical guidance to evaluate in vitro dermal absorption studies for pesticide registration: An industry perspective - Felix M. Kluxen; Edgars Felkers; Signe M. Jensen; JeanneY. Domoradzki; Christine Lorez; Philip Fisher; Christiane Wiemann (Regulatory Toxicology and Pharmacology, 2023)

Life satisfaction in coastal Kenya and Mozambique reflects culture, gendered relationships and security of basic needs: Implications for ecosystem services - Tim M. Daw; Nicole J. Reid; Sarah Coulthard; Tomas Chaigneau; Vilma Machava António; Christopher Cheupe; Geoff Wells; Edgar Bueno (Ecosystem Services, 2023)

Drivers of growth and establishment of the invasive plant Rumex acetosella within Andean fallow systems - Anna M. Visscher; Camilla Wellstein; Steven Vanek; Alessandro Bricca; Katherin Meza; Jhon Huaraca; Raul Ccanto; Edgar Olivera; José Loayza; Lionel Vigil; Samuel Palomino; Maria Scurrah; et al. (Agriculture, Ecosystems & Environment, 2023)

Morphology of buried volcanic bodies in a sedimentary basin of the Pacific Continental Shelf (Gulf of California, Mexico) - Mario González-Escobar; Abril C. Sánchez-Barra; Cristian A. Gallegos-Castillo; Sergio M. Arregui Ojeda; Edgar A. Mastache-Román (Journal of Volcanology and Geothermal Research, 2023)

Correction to: Protection by ordinary light clothing against pesticide spray drift for bystanders and residents - Edgars Felkers; Christian J. Kuster; Sarah Adham; Nicola J. Hewitt; Felix M. Kluxen (Journal of Consumer Protection and Food Safety, 2023)

Protection by ordinary light clothing against pesticide spray drift for bystanders and residents - Edgars Felkers; Christian J. Kuster; Sarah Adham; Nicola J. Hewitt; Felix M. Kluxen (Journal of Consumer Protection and Food Safety, 2023)
There are stringent EU regulatory requirements to assess pesticide exposure to bystanders and residents to direct spray drift. A “light clothing” adjustment factor (AF) of 0.82 is applied in the exposure assessment, based on simple assumptions for covered body surface and penetration through clothing. To assess the appropriateness of the AF, we collated data from 32 field studies. The mean and 25th percentile % reduction from ordinary light clothing (“reduction %”) in children and adults for all crops and standard and drift-reducing nozzles were 42.7% and 36.2%, resulting in AF of 0.573 and 0.638, respectively. Sources of variation were investigated, e.g. crop type, leaf coverage, buffer, spray pressure, and nozzle type, which indicated that reduction % could be impacted by several conditions. The reduction % is similar between crops; therefore, a single AF value covering all crops can be derived. One exception was for early-stage vineyard scenarios (the reduction % is lower (27%) than late stage (42–47%)) and could be considered individually to avoid unnecessary conservatism for the other scenarios. This evaluation demonstrates the current AF to be overly precautionary, and a more realistic, exposure scenario-relevant value could be applied for bystander/resident risk assessments.

Regional variability in peatland burning at mid-to high-latitudes during the Holocene - Thomas G. Sim; Graeme T. Swindles; Paul J. Morris; Andy J. Baird; Angela V. Gallego-Sala; Yuwan Wang; Maarten Blaauw; Philip Camill; Michelle Garneau; Mark Hardiman; Julie Loisel; Minna Vӓliranta; et al. (Quaternary Science Reviews, 2023)

The condition, use and future of the UK's largest accessible dinosaur tracksite at Spyway Quarry, Dorset - Kirsty M. Edgar; Luke E. Meade; Harry T. Jones; Lewis Haller; Sam Scriven; Christopher Reedman; Richard J. Butler (Proceedings of the Geologists' Association, 2023)

Evaluation of Moringa oleifera and corn starch as feed for seed production of the pearl oyster Pteria sterna (Gould,1851) - César Estay-Moyano; José M. Mazón-Suastegui; Edgar Zapata-Vívenes; César Lodeiros; Jesus Simal-Gandara (Aquaculture, 2023)

Tree-based land uses enhance the provision of ecosystem services in agricultural landscapes of the Peruvian highlands - Anna M. Visscher; Steven Vanek; Katherin Meza; Camilla Wellstein; Stefan Zerbe; Raul Ccanto; Edgar Olivera; Jhon Huaraca; Maria Scurrah; Steven J. Fonte (Agriculture, Ecosystems & Environment, 2023)

Dietary glutamine improves growth and intestinal morphology of juvenile GIFT tilapia (Oreochromis niloticus) but has limited effects on innate immunity and antioxidant capacity - Pedro L.P.F. Carvalho; William dos S. Xavier; Matheus G. Guimarães; Edgar J.D. Rodrigues; Wilson M. Furuya; Fernando Y. Yamamoto; Luiz E. Pezzato; Delbert M. Gatlin; Margarida M. Barros (Aquaculture, 2023)

Tectonic setting and mineralisation potential of the Cowley Ophiolite Complex, north Queensland - A. Edgar; I. V. Sanislav; P. H. G. M. Dirks (Australian Journal of Earth Sciences, 2022)

Dissection of race 1 anthracnose resistance in a watermelon (Citrullus lanatus var. lanatus) biparental mapping population - Bed Prakash Bhatta; Takshay Patel; Edgar Correa; Todd C. Wehner; Kevin M. Crosby; Michael J. Thomson; Richard Metz; Shichen Wang; Marcel Brun; Charles D. Johnson; Subas Malla (Euphytica, 2022)

Elevated [CO2] mitigates the impacts of heat stress in eucalyptus seedlings - Samuel S. Pinto; Auxiliadora O. Martins; Luiz F. P. Fontes; Franciele S. Oliveira; Iale C. Almeida; Iagor B. Detoni; Leonardo A. Oliveira; Willian B. Silva; David B. Medeiros; Edgar A. T. Picoli; Aristides Ribeiro; Alisdair R. Fernie; et al. (Theoretical and Experimental Plant Physiology, 2022)

A new conceptional model for deriving average dermal absorption estimates from studies with multiple tested concentrations for non-dietary risk assessment of pesticides - Felix M. Kluxen; Edgars Felkers; Steve McEuen; Philip Fisher; Christian Strupp; Christine Lorez; Jeanne Y. Domoradzki; Christiane Wiemann (Archives of Toxicology, 2022)
Dermal absorption values are used to translate external dermal exposure into potential systemic exposure for non-dietary risk assessment of pesticides. While the Environmental Protection Agency of the United States of America (US EPA) derives a common dermal absorption factor for active substances covering all related products, the European Food Safety Authority (EFSA) requests specific product-based estimates for individual concentrations covering the intended use rates. The latter poses challenges, because it disconnects exposure dose from applied dose in absorption studies, which may not be suitable in scenarios where concentration is not relevant. We analyzed the EFSA dermal absorption database, collected 33 human in vitro studies from CropLife Europe (CLE) companies, where ≥3 in-use dilution concentrations were tested, and 15 dermal absorption triple pack datasets. This shows that absolute dermal absorption correlates with absolute applied dose on a decadic logarithm-scale, which is concordant with the toxicological axiom that risk is driven by exposure dose. This method is radically different from the current European approach focused on concentrations and offers new insights into the relationship of internal and external exposure doses when utilizing data from in vitro studies. A single average dermal absorption value can be simply derived from studies with multiple tested concentrations, by calculating the y-intercept of a linear model on a decadic logarithm scale while assuming a slope of 1. This simplifies risk assessment and frees resources to explore exposure refinements. It also serves as a basis to harmonize dermal absorption estimation globally for use in exposure-driven risk assessments.

Increased Concentrations of Atherogenic Proteins in Aneurysm Sac Are Associated with Wall Enhancement of Unruptured Intracranial Aneurysm - Daizo Ishii; Alexander Choi; Anthony Piscopo; Zain Mehdi; Ashrita Raghuram; Mario Zanaty; Yongjun Lu; Edgar A. Samaniego; David M. Hasan (Translational Stroke Research, 2022)

Spatial compositional turnover varies with trophic level and body size in marine assemblages of micro‐ and macroorganisms - Amanda K. Pettersen; Melinda A. Coleman; Guillaume Latombe; Sebastian Vadillo Gonzalez; Nathan L. R. Williams; Justin R. Seymour; Alexandra H. Campbell; Torsten Thomas; Renata Ferrari; Rick D. Stuart‐Smith; Graham J. Edgar; Peter D. Steinberg; et al. (Global Ecology and Biogeography, 2022)
Aim Spatial compositional turnover varies considerably among co‐occurring assemblages of organisms, presumably shaped by common processes related to species traits. We investigated patterns of spatial turnover in a diverse set of marine assemblages using zeta diversity, which extends traditional pairwise measures of turnover to capture the roles of both rare and common species in shaping assemblage turnover. We tested the generality of hypothesized patterns related to ecological traits and provide insights into mechanisms of biodiversity change. Location Temperate pelagic and benthic marine assemblages of micro‐ and macroorganisms along south‐eastern Australia (30–36° S latitude). Time period 2008–2021. Major taxa studied Bacteria, phytoplankton, zooplankton, fish, and macrobenthic groups. Methods Six marine datasets spanning bacteria to fishes were collated for measures of “species” occurrence, with a 1° latitude grain. For each assemblage, ecological traits of body size, habitat and trophic level were analysed for the form and rate of decline in zeta diversity and for the species retention rate. Results Species at higher trophic levels showed two to three times the rate of zeta diversity decline compared with lower trophic levels, indicating an increase in turnover from phytoplankton to carnivorous fishes. Body size showed the hypothesized unimodal relationship with rates of turnover for macroorganisms. Patterns of bacterial turnover contrasted with those found for macroorganisms, with the highest levels of turnover in pelagic habitats compared with benthic (kelp‐associated) habitats. The shape of retention rate curves showed the importance of both rare and common species in driving turnover; a finding that would not have been observable using pairwise (beta diversity) measures of turnover. Main conclusions Our results support theoretical predictions for phytoplankton and macroorganisms, showing an increase in turnover rate with trophic level, but these predictions did not hold for bacteria. Such deviations from theory need to be investigated further to identify underlying processes that govern microbial assemblage dynamics.

RXam2, a NLR from cassava (Manihot esculenta) contributes partially to the quantitative resistance to Xanthomonas phaseoli pv. manihotis - Paula A. Díaz-Tatis; Juan C. Ochoa; Edgar M. Rico; Catalina Rodríguez; Adriana Medina; Boris Szurek; Paul Chavarriaga; Camilo E. López (Plant Molecular Biology, 2022)

Incidental burning on bones by Neanderthals: the role of fire in the Qa level of Abric Romaní rock-shelter (Spain) - Edgar Téllez; Palmira Saladié; Antonio Pineda; Juan Marín; Josep Vallverdú; M. Gema Chacón; Eudald Carbonell (Archaeological and Anthropological Sciences, 2022)

Tropicalization of temperate reef fish communities facilitated by urchin grazing and diversity of thermal affinities - Jasmin M. Schuster; Rick D. Stuart‐Smith; Graham J. Edgar; Amanda E. Bates (Global Ecology and Biogeography, 2022)
Aim Global declines in structurally complex habitats are reshaping both land‐ and seascapes in directions that affect the responses of biological communities to warming. Here, we test whether widespread loss of kelp habitats through sea urchin overgrazing systematically changes the sensitivity of fish communities to warming. Location Global temperate latitudes. Time period Modern. Major taxa studied Fishes. Methods Community shifts in thermal affinity related to habitat were assessed by simulating and comparing fish communities from 2271 surveys across 15 ecoregions. Results We found that fishes in kelp and urchin barrens differed in realized thermal affinities and range sizes, but only in regions where species pools had high variability in the thermal affinities of species. Barrens on warm temperate reefs host relatively more warm‐affinity fish species than neighbouring kelp beds, highlighting the acceleration of tropicalization processes facilitated by urchin grazing. In contrast, proportionally more cool‐affinity fishes colonize barrens at high temperate latitudes, contributing to community lags with ocean warming in these regions. Main conclusions Our findings implicate urchins as drivers of ecological change, in part by affecting ecological resilience to warming.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Characterization of lipid droplets from a Taxus media cell suspension and their potential involvement in trafficking and secretion of paclitaxel - Abdulsamie Hanano; Edgar Perez-Matas; Mouhnad Shaban; Rosa M. Cusido; Denis J. Murphy (Plant Cell Reports, 2022)

Safeguarding marine life: conservation of biodiversity and ecosystems - Delphi Ward; Jessica Melbourne-Thomas; Gretta T. Pecl; Karen Evans; Madeline Green; Phillipa C. McCormack; Camilla Novaglio; Rowan Trebilco; Narissa Bax; Madeleine J. Brasier; Emma L. Cavan; Graham Edgar; et al. (Reviews in Fish Biology and Fisheries, 2022)
Marine ecosystems and their associated biodiversity sustain life on Earth and hold intrinsic value. Critical marine ecosystem services include maintenance of global oxygen and carbon cycles, production of food and energy, and sustenance of human wellbeing. However marine ecosystems are swiftly being degraded due to the unsustainable use of marine environments and a rapidly changing climate. The fundamental challenge for the future is therefore to safeguard marine ecosystem biodiversity, function, and adaptive capacity whilst continuing to provide vital resources for the global population. Here, we use foresighting/hindcasting to consider two plausible futures towards 2030: a business-as-usual trajectory (i.e. continuation of current trends), and a more sustainable but technically achievable future in line with the UN Sustainable Development Goals. We identify key drivers that differentiate these alternative futures and use these to develop an action pathway towards the desirable, more sustainable future. Key to achieving the more sustainable future will be establishing integrative (i.e. across jurisdictions and sectors), adaptive management that supports equitable and sustainable stewardship of marine environments. Conserving marine ecosystems will require recalibrating our social, financial, and industrial relationships with the marine environment. While a sustainable future requires long-term planning and commitment beyond 2030, immediate action is needed to avoid tipping points and avert trajectories of ecosystem decline. By acting now to optimise management and protection of marine ecosystems, building upon existing technologies, and conserving the remaining biodiversity, we can create the best opportunity for a sustainable future in 2030 and beyond.

Seismic vulnerability through drift assessment for bridges with geometrical irregularities - M. Consolación Gómez-Soberón; Edgar Pérez; Daymaru Salas; David De León-Escobedo (European Journal of Environmental and Civil Engineering, 2022)

Effect of replacing surface with underground rubbish containers on urban House Sparrows Passer domesticus - Edgar Bernat-Ponce; David Ferrer; José A. Gil-Delgado; Germán M. López-Iborra (Urban Ecosystems, 2022)
Urbanisation processes are increasing worldwide at surprising rates affecting wildlife in many ways: changing habitat structure, reducing resources, and modifying the distribution, composition and abundance of local biota. In different countries, urban waste collection techniques are evolving and surface rubbish containers (neighbourhood receptacles for temporarily storing anthropogenic household waste located above-ground on the streets) are being replaced with underground ones (metal boxes with steel chutes that fed into large underground containers) to improve sanitation measures, to avoid bad smells and waste scattering by animals. We aimed to detect if House Sparrows were more abundant close to surface rubbish containers than close to the underground ones. We recorded an abundance index of House Sparrows during two visits in winter 2018–2019 to point counts located in groups of both container types (80 and 85 groups of underground and surface containers, respectively) in eight towns of Eastern Spain. We modelled the abundance index according to rubbish container type, and 14 other environmental variables at four scales: container, nearest buildings, near urban features, and general locality features using GLMMs. House Sparrows were more abundant close to surface than to underground rubbish containers, which may be linked with higher food debris availability. The presence of other urban features (bar terraces, private gardens, mature trees) interacting with the rubbish containers also influenced the abundance of House Sparrows. The replacement of above-ground rubbish containers with underground ones may deprive House Sparrows resources, which could lead to the decline of this species, especially in urban areas with little green cover.

Toward the development of subnational hybrid input–output tables in a multiregional framework - Edgar Towa; Vanessa Zeller; Stefano Merciai; Jannick Schmidt; Wouter M. J. Achten (Journal of Industrial Ecology, 2022)
Environmental input–output analyses can be a useful decision support tool at the subnational level, because of its ability to capture economic and environmental impacts at other geographical levels. Yet, such analyses are hindered by the lack of subnational IO tables. Furthermore, the lack of physical product and waste flows in what is known as a “hybrid” table prevents a range of consumption‐based and circular‐economy‐type analyses. We demonstrate the development of a multiregional hybrid IOT (MRHIOT) along with environmental extensions at the subnational level and exemplify it for the case of Belgium. The development procedure discloses a novel approach of combining national hybrid tables, subnational monetary tables, and physical survey‐based data. Such a combination builds upon a partial‐survey approach that includes a range of techniques for initial estimation and reconciliation within a balancing procedure. For the validation of the approaches, we assessed the magnitude of deviations between the initial and final estimates and analyzed the uncertainties inherent to each initial estimation procedure. Subsequently, we conducted a consumption‐based analysis where we assessed the carbon footprint (CF) at the subnational level and highlighted the CF inherent to the interregional linkages. This study provides methodological and application‐based contributions to the discussion on the relevance of hybrid subnational tables and analyses compared to national ones. The proposed approach could be replicable to some extent for further developing subnational MRHIOT. The study is expected to foster more research toward the development of further subnational MRHIOT as well as its associated wide‐ranging applications.

Correction to: Characterizing introgression‑by‑environment interactions using maize near isogenic lines - Zhi Li; Sara B. Tirado; Dnyaneshwar C. Kadam; Lisa Coffey; Nathan D. Miller; Edgar P. Spalding; Aaron J. Lorenz; Natalia de Leon; Shawn M. Kaeppler; Patrick S. Schnable; Nathan M. Springer; Candice N. Hirsch (Theoretical and Applied Genetics, 2021)

The elasmobranchs of Malpelo Flora and Fauna Sanctuary , Colombia - Sandra Bessudo; Felipe Ladino; Edgar Eduardo Becerril‐García; Charles M. Shepard; Pelayo Salinas‐De‐León; Edgar Mauricio Hoyos‐Padilla (Journal of Fish Biology, 2021)
Management and conservation actions in marine‐protected areas require baselines for monitoring threatened marine fauna such as elasmobranchs. This article provides evidence of the occurrence of 34 species of elasmobranchs (21 sharks and 13 batoids) in the Malpelo Flora and Fauna Sanctuary, Colombia, including five new records of sharks and three of rays. From 1987 to 2021, new records were obtained by underwater visual census using SCUBA, manned submersibles and deep‐ocean cameras to depths of up to 2211 m. Of the recorded species, 21 are considered as threatened taxa (64%) by the IUCN, making the Malpelo Flora and Fauna Sanctuary an essential conservation area for this highly threatened group of species.

The use of an unoccupied aerial vehicle to survey shark species over sand and rocky‐reef habitats in a marine protected area - Kathryn A. Ayres; James T. Ketchum; Rogelio González‐Armas; Felipe Galván‐Magaña; Alex Hearn; Fernando R. Elorriaga‐Verplancken; Edgar M. Hoyos‐Padilla; Stephen M. Kajiura (Journal of Fish Biology, 2021)
Cabo Pulmo National Park was established in 1995 and has since seen a large increase in fish biomass. An unoccupied aerial vehicle (UAV) was used to survey shallow coastal habitat in which lemon sharks ( Negaprion brevirostris ), bull sharks ( Carcharhinus leucas ) and Pacific nurse sharks ( Ginglymostoma unami ) were recorded. Sharks were more common in the afternoon, potentially using warmer shallow areas to behaviourally thermoregulate. This study highlights UAV surveying to be a viable tool for species identification, a limitation of previous terrestrial surveys conducted in the area.

Seasonal reproductive synchrony in colonies of the Jamaican fruit–eating bat (Artibeus jamaicensis) in southeast Mexico - Jorge Ortega; Edgar G. Gutiérrez; Diana D. Moreno-Santillán; M. Cristina MacSwiney G (Mammal Research, 2021)

Reef communities show predictable undulations in linear abundance size spectra from copepods to sharks - Freddie J. Heather; Rick D. Stuart‐Smith; Julia L. Blanchard; Kate M. Fraser; Graham J. Edgar (Ecology Letters, 2021)
Among the more widely accepted general hypotheses in ecology is that community relationships between abundance and body size follow a log‐linear size spectrum, from the smallest consumers to the largest predators (i.e. ‘bacteria to whales’). Nevertheless, most studies only investigate small subsets of this spectrum, and note that extreme size classes in survey data deviate from linear expectations. In this study, we fit size spectra to field data from 45 rocky and coral reef sites along a 28° latitudinal gradient, comprising individuals from 0.125 mm to 2 m in body size. We found that 96% of the variation in abundance along this ‘extended’ size gradient was described by a single linear function across all sites. However, consistent ‘wobbles’ were also observed, with subtle peaks and troughs in abundance along the spectrum, which varied with sea temperature, as predicted by theory relating to trophic cascades.

Detecting Mollicutes by PCR in goats in southwestern Bahia, Brazil - Regis Edgar Castilho Junior; Carlos Augusto Scacchetti de Almeida; Verena M. Santos; Aline T. Amorim; Natália C. Gaeta; Izadora R. Souza; Maysa B Santos; Guilherme B. Campos; Luiz Eduardo Barreto de Souza; Jurandir Ferreira da Cruz; Nilson Roberti Benites; Lucas Miranda Marques; et al. (Brazilian Journal of Microbiology, 2021)

Assessing the circularity of regions: Stakes of trade of waste for treatment - Edgar Towa; Vanessa Zeller; Wouter M. J. Achten (Journal of Industrial Ecology, 2021)
The degree of circularity of a region describes the proportion of materials recovered and reintroduced in that region of the total materials in that region. Quantifying the degree of circularity of a region is important, to prioritize and adequately implement circular economy (CE) strategies. Besides, regions may import and export waste treatment services. Efficient CE strategies should integrate the circularity embodied in the interregional linkages regarding waste treatment. However, the existing analyses of the degree of circularity of regions do not consider the trade of waste for treatment between regions. We fill this gap by proposing the trade‐corrected circularity index and trade‐corrected circularity gap index as two novel indicators, including their methodology and application for the case of Belgian regions. We used the multiregional physical supply and use the table we previously developed at the subnational Belgian level for 2011 and focused on Brussels, Flanders, and Wallonia. The results show that Brussels, Flanders, and Wallonia are 0%, 6.3%, and 8.1% circular , respectively, and when considering the trade of waste for treatment, they are 7.7%, 6%, and 8.5% circular , respectively. Further results include details of the circularity per type of materials (biomass, fossil fuels, metals, and non‐metallic minerals) as well as the circularity inherent to the trade of waste between regions. This paper ends with a discussion on the methodological and conceptual findings, the CE policy implications, and the contributions to the debate on measuring the circularity of regions when the trade of waste is at stake.

High biomass and productivity of epifaunal invertebrates living amongst dead coral - Kate M. Fraser; Rick D. Stuart-Smith; Scott D. Ling; Graham J. Edgar (Marine Biology, 2021)

Assessing the Quality of Amazon Aquatic Ecosystems with Multiple Lines of Evidence: The Case of the Northeast Andean Foothills of Ecuador - Emily Galarza; Marcela Cabrera; Rodrigo Espinosa; Edgar Espitia; Gabriel M. Moulatlet; Mariana V. Capparelli (Bulletin of Environmental Contamination and Toxicology, 2021)

Assessing the Impact of 41 Years of Forest Management on Native Wildlife Habitat in Minnesota, USA - John M Zobel; Alan R Ek; Christopher B Edgar (Journal of Forestry, 2021)
Over the last four decades, forest management goals have transitioned to multiuse objectives, begging the question of their impact on wildlife habitat. Using USDA Forest Service Forest Inventory and Analysis data and the WHINGS (Wildlife Habitat Indicator for Native Genera and Species) model, the trends in wildlife habitat were quantified from 1977 to 2018 across Minnesota. Statewide, 35.5% of species experienced significant improvement in habitat, 29% significant reductions, and 35.5% nonsignificant change. The extent of habitat (acreage) increased for 100% of species, but the quality declined for 63% of species. Results were explained by the reduction in acreage of larger size classes of the aspen, balsam, and birch forest type and increases in smaller, younger forest area. Specifically, forest management that converted aspen stands to other forest types benefited certain wildlife species over others. Future forest management should consider the balance between the habitat requirements of the diverse native species in Minnesota. Study Implications Trends in forest wildlife habitat over the last four decades across Minnesota highlight that forest management often favors one species at the expense of another. Statewide, wildlife species with preferences for larger, older aspen experienced diminished habitat, whereas habitat for species preferring younger forest types or older nonaspen types increased. Regionally, the forested ecoregions in Minnesota (northeast) generally saw reduced habitat, whereas the prairie/agricultural regions (south and northwest) saw the largest increases. Through this and further applications, forest and wildlife managers can rapidly assess the habitat implications of proposed management, whether for environmental review, forest planning, or harvest scheduling.

Prevalence and genetic diversity of Shibuyunji virus, a novel tick-borne phlebovirus identified in Zambia - Edgar Simulundu; Saidon Mbambara; Herman M. Chambaro; Karen Sichibalo; Masahiro Kajihara; King S. Nalubamba; Hirofumi Sawa; Ayato Takada; Katendi Changula; Simbarashe Chitanga (Archives of Virology, 2021)

Serratia sp., an endophyte of Mimosa pudica nodules with nematicidal, antifungal activity and growth-promoting characteristics - Erick Williams Méndez-Santiago; Olga Gómez-Rodríguez; Ricardo Sánchez-Cruz; Jorge Luis Folch-Mallol; Victor M. Hernández-Velázquez; Edgar Villar-Luna; Liliana Aguilar-Marcelino; Arnoldo Wong-Villarreal (Archives of Microbiology, 2021)

The use of machine learning to detect foraging behaviour in whale sharks: a new tool in conservation - Darren A. Whitehead; Felipe G. Magaña; James T. Ketchum; Edgar M. Hoyos; Rogelio G. Armas; Francesca Pancaldi; Damien Olivier (Journal of Fish Biology, 2021)
In this study we present the first attempt at modelling the feeding behaviour of whale sharks using a machine learning analytical method. A total of eight sharks were monitored with tri‐axial accelerometers and their foraging behaviours were visually observed. Our results highlight that the random forest model is a valid and robust approach to predict the feeding behaviour of the whale shark. In conclusion this novel approach exposes the practicality of this method to serve as a conservation tool and the capability it offers in monitoring potential disturbances of the species.

Human Health Risk Assessment Due to Agricultural Activities and Crop Consumption in the Surroundings of an Industrial Area - Marina M. S. Cabral-Pinto; Manuela Inácio; Orquídia Neves; Agostinho A. Almeida; Edgar Pinto; Bárbara Oliveiros; Eduardo A. Ferreira da Silva (Exposure and Health, 2020)

An estimate of the number of white sharks Carcharodon carcharias interacting with ecotourism in G uadalupe I sland - Edgar E. Becerril‐García; Edgar M. Hoyos‐Padilla; Omar Santana‐Morales; Miguel A. Gutiérrez‐Ortiz; Arturo Ayala‐Bocos; Felipe Galván‐Magaña (Journal of Fish Biology, 2020)
The aim of the present study is to provide an estimate of the number of white sharks Carcharodon carcharias that seasonally interact with ecotourism boats in Guadalupe Island using Schnabel's mark–recapture method and 6316 records of white sharks during 2012–2014. The results of the estimation highlight an abundance of 78 white sharks 95% C.I. (62.1, 105.6) interacting with ecotourism. The regulations regarding the number of tourists, boats and the monitoring of white sharks should be assessed to improve management decisions regarding the conservation and sustainable use of this threatened species.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Characterizing introgression-by-environment interactions using maize near isogenic lines - Zhi Li; Sara B. Tirado; Dnyaneshwar C. Kadam; Lisa Coffey; Nathan D. Miller; Edgar P. Spalding; Aaron J. Lorenz; Natalia de Leon; Shawn M. Kaeppler; Patrick S. Schnable; Nathan M. Springer; Candice N. Hirsch (Theoretical and Applied Genetics, 2020)

Sharks, rays, and chimaeras of the Revillagigedo National Park: An update of new and confirmed records - Edgar E. Becerril‐García; Edgar M. Hoyos‐Padilla; Brad Henning; Pelayo Salinas‐De León (Journal of Fish Biology, 2020)
The Revillagigedo Archipelago National Park is the largest no‐take Marine Protected Area in North America and it is essential for the conservation of globally endangered marine megafauna, including cetaceans, sea birds and cartilaginous fishes. The present paper reports the occurrence of 28 chondrichthyan species, including 19 sharks, seven batoids and two chimaeras in the Revillagigedo Archipelago, comprising eight new records and a brief revision of confirmed species to date.

Treatment with One Dose of Reltecimod is Superior to Two Doses in Mouse Models of Lethal Infection - Rotem Edgar; Margarite L. Tarrio; Greg Maislin; Feng Chiguang; Raymond Kaempfer; Alan Cross; Steven M. Opal; Anat Shirvan (International Journal of Peptide Research and Therapeutics, 2020)

When the Source of Flooding Matters: Divergent Responses in Carbon Fluxes in an Alaskan Rich Fen to Two Types of Inundation - E. S. Euskirchen; E. S. Kane; C. W. Edgar; M. R. Turetsky (Ecosystems, 2020)

Neurologic, clinical, and immunologic features in a cohort of HTLV-1 carriers with high proviral loads - Sheila N. Ferraz; Gabriela F. Costa; José Abraão Carneiro Neto; Thiago Hebert; Cassius J. V. de Oliveira; Mariele Guerra; Lívia M. A. Oliveira; Edgar M. Carvalho (Journal of NeuroVirology, 2020)
A high proviral load (PVL) is recognized as a risk factor for human T cell leukemia virus-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP), but there is a lack of prospective studies evaluating whether or not HTLV-1 carriers with high PVL are at risk of developing HAM/TSP or other HTLV-1-related diseases. Here, we compare the incidence of clinical manifestations and the cytokine levels in 30 HTLV-1 carriers with high (> 50,000 copies/10 6 PBMC) and an equal number of subjects with low proviral load. Participants were followed for 3 to 16 years (median of 11 years). The PVL, IFN-γ, TNF, and IL-10 levels were quantified at entry and at the end of the follow-up. Among the self-reported symptoms in the initial evaluation, only the presence of paresthesia on the hands was more frequent in the group with high PVL ( p < 0.04). The production of IFN-γ was higher in the group with high PVL group (median of 1308 versus 686 pg/ml, p < 0.011) when compared with the control group in the first assessment. There was no difference in the occurrence of urinary symptoms or erectile dysfunction, periodontal disease, Sicca syndrome, and neurologic signs between the two groups during the follow-up. The observation that none of the HTLV-1 carriers with high PVL and with exaggerated inflammatory response progressed to HAM/TSP indicates that other factors in addition to the PVL and an exaggerated immune response are involved in the pathogenesis of HAM/TSP.

Replacement of semi-natural cover with artificial substrates in urban parks causes a decline of house sparrows Passer domesticus in Mediterranean towns - Edgar Bernat-Ponce; José A. Gil-Delgado; Germán M. López-Iborra (Urban Ecosystems, 2020)

Correction to: CpG‑creating mutations are costly in many human viruses - Victoria R. Caudill; Sarina Qin; Ryan Winstead; Jasmeen Kaur; Kaho Tisthammer; E. Geo Pineda; Caroline Solis; Sarah Cobey; Trevor Bedford; Oana Carja; Rosalind M. Eggo; Katia Koelle; et al. (Evolutionary Ecology, 2020)

CpG-creating mutations are costly in many human viruses - Victoria R. Caudill; Sarina Qin; Ryan Winstead; Jasmeen Kaur; Kaho Tisthammer; E. Geo Pineda; Caroline Solis; Sarah Cobey; Trevor Bedford; Oana Carja; Rosalind M. Eggo; Katia Koelle; et al. (Evolutionary Ecology, 2020)
Mutations can occur throughout the virus genome and may be beneficial, neutral or deleterious. We are interested in mutations that yield a C next to a G, producing CpG sites. CpG sites are rare in eukaryotic and viral genomes. For the eukaryotes, it is thought that CpG sites are rare because they are prone to mutation when methylated. In viruses, we know less about why CpG sites are rare. A previous study in HIV suggested that CpG-creating transition mutations are more costly than similar non-CpG-creating mutations. To determine if this is the case in other viruses, we analyzed the allele frequencies of CpG-creating and non-CpG-creating mutations across various strains, subtypes, and genes of viruses using existing data obtained from Genbank, HIV Databases, and Virus Pathogen Resource. Our results suggest that CpG sites are indeed costly for most viruses. By understanding the cost of CpG sites, we can obtain further insights into the evolution and adaptation of viruses.

An Inter-disciplinary Approach to Evaluate Human Health Risks Due to Long-Term Exposure to Contaminated Groundwater Near a Chemical Complex - Marina M. S. Cabral Pinto; Carlos M. Ordens; M. Teresa Condesso de Melo; Manuela Inácio; Agostinho Almeida; Edgar Pinto; Eduardo A. Ferreira da Silva (Exposure and Health, 2020)

Mexico ants: incidence and abundance along the Nearctic–Neotropical interface - Wesley Dáttilo; Miguel Vásquez‐Bolaños; Diana A. Ahuatzin; Reuber Antoniazzi; Edgar Chávez‐González; Erick Corro; Pedro Luna; Roger Guevara; Fabricio Villalobos; Ricardo Madrigal‐Chavero; Jéssica C. de Faria Falcão; Adrián Bonilla‐Ramírez; et al. (Ecology, 2020)
Mexico is one of the most biodiverse countries in the world, with an important proportion of endemism mainly because of the convergence of the Nearctic and Neotropical biogeographic regions, which generate great diversity and species turnover at different spatial scales. However, most of our knowledge of the Mexican ant biota is limited to a few well‐studied taxa, and we lack a comprehensive synthesis of ant biodiversity information. For instance, most of the knowledge available in the literature on Mexican ant fauna refers only to species lists by states, or is focused on only a few regions of the country, which prevents the study of several basic and applied aspects of ants, from diversity and distribution to conservation. Our aims in this data paper are therefore (1) to compile all the information available regarding ants across the Mexican territory, and (2) to identify major patterns in the gathered data set and geographic gaps in order to direct future sampling efforts. All records were obtained from raw data, including both unpublished and published information. After exhaustive filtering and updating information and synonyms, we compiled a total of 21,731 records for 887 ant species distributed throughout Mexico from 1894 to 2018. These records were concentrated mainly in the states of Chiapas ( n = 6,902, 32.76%) and Veracruz de Ignacio de la Llave ( n = 4,329, 19.92%), which together comprise half the records. The subfamily with the highest number of records was Myrmicinae ( n = 10,458 records, 48.12%), followed by Formicinae ( n = 3,284, 15.11%) and Ponerinae ( n = 1,914, 8.8%). Most ant records were collected in the Neotropical region of the country ( n = 12,646, 58.19%), followed by the Mexican transition zone ( n = 5,237, 24.09%) and the Nearctic region ( n = 3,848, 17.72%). Native species comprised 95.46% of the records ( n = 20,745). To the best of our knowledge, this is the most complete data set available to date in the literature for the country. We hope that this compilation will encourage researchers to explore different aspects of the population and community research of ants at different spatial scales, and to aid in the establishment of conservation policies and actions. There are no copyright restrictions. Please cite this data paper when using its data for publications or teaching events.

Automated lifespan determination across Caenorhabditis strains and species reveals assay-specific effects of chemical interventions - Stephen A. Banse; Mark Lucanic; Christine A. Sedore; Anna L. Coleman-Hulbert; W. Todd Plummer; Esteban Chen; Jason L. Kish; David Hall; Brian Onken; Michael P. Presley; E. Grace Jones; Benjamin W. Blue; et al. (GeroScience, 2019)
The goal of the Caenorhabditis Intervention Testing Program is to identify robust and reproducible pro-longevity interventions that are efficacious across genetically diverse cohorts in the Caenorhabditis genus. The project design features multiple experimental replicates collected by three different laboratories. Our initial effort employed fully manual survival assays. With an interest in increasing throughput, we explored automation with flatbed scanner-based Automated Lifespan Machines (ALMs). We used ALMs to measure survivorship of 22 Caenorhabditis strains spanning three species. Additionally, we tested five chemicals that we previously found extended lifespan in manual assays. Overall, we found similar sources of variation among trials for the ALM and our previous manual assays, verifying reproducibility of outcome. Survival assessment was generally consistent between the manual and the ALM assays, although we did observe radically contrasting results for certain compound interventions. We found that particular lifespan outcome differences could be attributed to protocol elements such as enhanced light exposure of specific compounds in the ALM, underscoring that differences in technical details can influence outcomes and therefore interpretation. Overall, we demonstrate that the ALMs effectively reproduce a large, conventionally scored dataset from a diverse test set, independently validating ALMs as a robust and reproducible approach toward aging-intervention screening.

Effects of Roughness Loss on Reef Hydrodynamics and Coastal Protection: Approaches in Latin America - Juan D. Osorio-Cano; Juan C. Alcérreca-Huerta; Ismael Mariño-Tapia; Andrés F. Osorio; Cesar Acevedo-Ramírez; Cecilia Enriquez; Mirella Costa; Pedro Pereira; Edgar Mendoza; Mireille Escudero; Alejandro Astorga-Moar; José López-González; et al. (Estuaries and Coasts, 2019)

The Incorporation of Biophysical and Social Components in Coastal Management - Rodolfo Silva; Valeria Chávez; Tjeerd J. Bouma; Brigitta I. van Tussenbroek; Katie K. Arkema; M. Luisa Martínez; Hocine Oumeraci; Johanna J. Heymans; Andrés F. Osorio; Edgar Mendoza; Malva Mancuso; Milton Asmus; et al. (Estuaries and Coasts, 2019)

Does the Functional Richness of Plants Reduce Wave Erosion on Embryo Coastal Dunes? - Carmelo Maximiliano-Cordova; Karla Salgado; M. Luisa Martínez; Edgar Mendoza; Rodolfo Silva; Roger Guevara; Rusty A. Feagin (Estuaries and Coasts, 2019)

Refugia under threat: Mass bleaching of coral assemblages in high‐latitude eastern Australia - Sun W. Kim; Eugenia M. Sampayo; Brigitte Sommer; Carrie A. Sims; Maria del C. Gómez‐Cabrera; Steve J. Dalton; Maria Beger; Hamish A. Malcolm; Renata Ferrari; Nicola Fraser; Will F. Figueira; Stephen D. A. Smith; et al. (Global Change Biology, 2019)
Environmental anomalies that trigger adverse physiological responses and mortality are occurring with increasing frequency due to climate change. At species' range peripheries, environmental anomalies are particularly concerning because species often exist at their environmental tolerance limits and may not be able to migrate to escape unfavourable conditions. Here, we investigated the bleaching response and mortality of 14 coral genera across high‐latitude eastern Australia during a global heat stress event in 2016. We evaluated whether the severity of assemblage‐scale and genus‐level bleaching responses was associated with cumulative heat stress and/or local environmental history, including long‐term mean temperatures during the hottest month of each year (SST LTMAX ), and annual fluctuations in water temperature (SST VAR ) and solar irradiance (PARZ VAR ). The most severely‐bleached genera included species that were either endemic to the region ( Pocillopora aliciae ) or rare in the tropics (e.g. Porites heronensis ). Pocillopora spp., in particular, showed high rates of immediate mortality. Bleaching severity of Pocillopora was high where SST LTMAX was low or PARZ VAR was high, whereas bleaching severity of Porites was directly associated with cumulative heat stress. While many tropical Acropora species are extremely vulnerable to bleaching, the Acropora species common at high latitudes, such as A. glauca and A. solitaryensis , showed little incidence of bleaching and immediate mortality. Two other regionally‐abundant genera, Goniastrea and Turbinaria , were also largely unaffected by the thermal anomaly. The severity of assemblage‐scale bleaching responses was poorly explained by the environmental parameters we examined. Instead, the severity of assemblage‐scale bleaching was associated with local differences in species abundance and taxon‐specific bleaching responses. The marked taxonomic disparity in bleaching severity, coupled with high mortality of high‐latitude endemics, point to climate‐driven simplification of assemblage structures and progressive homogenisation of reef functions at these high‐latitude locations.

Corrigendum: A Response to Scientific and Societal Needs for Marine Biological Observations - Nicholas J. Bax; Patricia Miloslavich; Frank Edgar Muller-Karger; Valerie Allain; Ward Appeltans; Sonia Dawn Batten; Lisandro Benedetti-Cecchi; Pier Luigi Buttigieg; Sanae Chiba; Daniel Paul Costa; J. Emmett Duffy; Daniel C. Dunn; et al. (Frontiers in Marine Science, 2019)

Molecular detection and characterization of genotype 1 bovine leukemia virus from beef cattle in the traditional sector in Zambia - Mundia M. Phiri; Evans Kaimoyo; Katendi Changula; Isaac Silwamba; Herman M. Chambaro; Penjaninge Kapila; Masahiro Kajihara; Martin Simuunza; John Bwalya Muma; Girja S. Pandey; Ayato Takada; Aaron S. Mweene; et al. (Archives of Virology, 2019)

Fingernail Trace Element Content in Environmentally Exposed Individuals and Its Influence on Their Cognitive Status in Ageing - Marina M. S. Cabral Pinto; A. Paula Marinho-Reis; Agostinho Almeida; Sandra Freitas; Mário R. Simões; M. Luísa Diniz; Edgar Pinto; Patrícia Ramos; Eduardo Ferreira da Silva; Paula I. Moreira (Exposure and Health, 2019)

A Response to Scientific and Societal Needs for Marine Biological Observations - Nicholas J. Bax; Patricia Miloslavich; Frank Edgar Muller-Karger; Valerie Allain; Ward Appeltans; Sonia Dawn Batten; Lisandro Benedetti-Cecchi; Pier Luigi Buttigieg; Sanae Chiba; Daniel Paul Costa; J. Emmett Duffy; Daniel C. Dunn; et al. (Frontiers in Marine Science, 2019)

Toward a Coordinated Global Observing System for Seagrasses and Marine Macroalgae - J. Emmett Duffy; Lisandro Benedetti-Cecchi; Joaquin Trinanes; Frank E. Muller-Karger; Rohani Ambo-Rappe; Christoffer Boström; Alejandro H. Buschmann; Jarrett Byrnes; Robert G. Coles; Joel Creed; Leanne C. Cullen-Unsworth; Guillermo Diaz-Pulido; et al. (Frontiers in Marine Science, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Urinary metabolites of the UV filter octocrylene in humans as biomarkers of exposure - Daniel Bury; Hendrik Modick-Biermann; Edgar Leibold; Thomas Brüning; Holger M. Koch (Archives of Toxicology, 2019)

A taxonomic review of Myriocladus (Poaceae, Bambusoideae) in Brazil, including the description of a new species - Edgar A. L. Afonso; Santelmo Vasconcelos; Benjamin M. Torke; Pedro L. Viana (Brittonia, 2019)

Diaphorocleidus machacae n. sp. (Monogenea) Infecting the Gill Lamellae of Brycon guatemalensis (Characiformes: Bryconidae) from the Rio Lacantún Basin in Chiapas, Mexico - Edgar F. Mendoza-Franco; Juan M. Caspeta-Mandujano; Carlos Ramírez-Martínez (Acta Parasitologica, 2019)

Body size, reef area and temperature predict global reef‐fish species richness across spatial scales - D. R. Barneche; E. L. Rezende; V. Parravicini; E. Maire; G. J. Edgar; R. D. Stuart‐Smith; J. E. Arias‐González; C. E. L. Ferreira; A. M. Friedlander; A. L. Green; O. J. Luiz; F. A. Rodríguez‐Zaragoza; et al. (Global Ecology and Biogeography, 2019)
Aim To investigate biotic and abiotic correlates of reef‐fish species richness across multiple spatial scales. Location Tropical reefs around the globe, including 485 sites in 109 sub‐provinces spread across 14 biogeographic provinces. Time period Present. Major taxa studied 2,523 species of reef fish. Methods We compiled a database encompassing 13,050 visual transects. We used hierarchical linear Bayesian models to investigate whether fish body size, reef area, isolation, temperature, and anthropogenic impacts correlate with reef‐fish species richness at each spatial scale (i.e., sites, sub‐provinces, provinces). Richness was estimated using coverage‐based rarefaction. We also tested whether species packing (i.e., transect‐level species richness/m 2 ) is correlated with province‐level richness. Results Body size had the strongest effect on species richness across all three spatial scales. Reef area and temperature were both positively correlated with richness at all spatial scales. At the site scale only, richness decreased with reef isolation. Species richness was not correlated with proxies of human impacts. Species packing was correlated with species richness at the province level following a sub‐linear power function. Province‐level differences in species richness were also mirrored by patterns of body size distribution at the site scale. Species‐rich provinces exhibited heterogeneous assemblages of small‐bodied species with small range sizes, whereas species‐poor provinces encompassed homogeneous assemblages composed by larger species with greater dispersal capacity. Main conclusions Our findings suggest that body size distribution, reef area and temperature are major predictors of species richness and accumulation across scales, consistent with recent theories linking home range to species–area relationships as well as metabolic effects on speciation rates. Based on our results, we hypothesize that in less diverse areas, species are larger and likely more dispersive, leading to larger range sizes and less turnover between sites. Our results indicate that changes in province‐level (i.e., regional) richness should leave a tractable fingerprint in local assemblages, and that detailed studies on local‐scale assemblage composition may be informative of responses occurring at larger scales.

Comparative features between recombinant lipases CALA-like from U. maydis and CALA from C. antarctica in thermal stability and selectivity - Marcela Robles-Machuca; M. Martin del Campo; M. Ángeles Camacho-Ruiz; Enrique Ordaz; Edgar O. Zamora-González; Marcelo Müller-Santos; Jorge A. Rodríguez (Biotechnology Letters, 2019)

Correction to: Differential recognition of natural and remodeled glycotopes by three Diocleae lectins - Tania M. Cortázar; Iain B. H. Wilson; Alba Hykollari; Edgar A. Reyes; Nohora A. Vega (Glycoconjugate Journal, 2019)

Future Research Directions on the “Elusive” White Shark - Charlie Huveneers; Kirin Apps; Edgar E. Becerril-García; Barry Bruce; Paul A. Butcher; Aaron B. Carlisle; Taylor K. Chapple; Heather M. Christiansen; Geremy Cliff; Tobey H. Curtis; Toby S. Daly-Engel; Heidi Dewar; et al. (Frontiers in Marine Science, 2018)

Effects of Pollution From Anthropogenic Point Sources on the Recruitment of Sessile Estuarine Reef Biota - Amelia E. Fowles; Graham J. Edgar; Rick D. Stuart-Smith; James B. Kirkpatrick; Nicole Hill; Russell J. Thomson; Elisabeth M. A. Strain (Frontiers in Marine Science, 2018)

Front Cover - Pietro Kiyoshi Maruyama; Jesper Sonne; Jeferson Vizentin‐Bugoni; Ana M. Martín González; Thais B. Zanata; Stefan Abrahamczyk; Ruben Alarcón; Andréa C. Araujo; Francielle P. Araújo; Andrea C. Baquero; Edgar Chávez‐González; Aline G. Coelho; et al. (Global Ecology and Biogeography, 2018)

Functional diversity mediates macroecological variation in plant–hummingbird interaction networks - Pietro Kiyoshi Maruyama; Jesper Sonne; Jeferson Vizentin‐Bugoni; Ana M. Martín González; Thais B. Zanata; Stefan Abrahamczyk; Ruben Alarcón; Andréa C. Araujo; Francielle P. Araújo; Andrea C. Baquero; Edgar Chávez‐González; Aline G. Coelho; et al. (Global Ecology and Biogeography, 2018)
Aim Species interaction networks are known to vary in structure over large spatial scales. We investigated the hypothesis that environmental factors affect interaction network structure by influencing the functional diversity of ecological communities. Notably, we expect more functionally diverse communities to form interaction networks with a higher degree of niche partitioning. Location: Americas. Time period: Current. Major taxa studied: Hummingbirds and their nectar plants. Methods We used a large dataset comprising 74 quantitative plant–hummingbird interaction networks distributed across the Americas, along with morphological trait data for 158 hummingbird species. First, we used a model selection approach to evaluate associations between the environment (climate, topography and insularity), species richness and hummingbird functional diversity as predictors of network structure (niche partitioning, i.e., complementary specialization and modularity). Second, we used structural equation models (SEMs) to ask whether environmental predictors and species richness affect network structure directly and/or indirectly through their influence on hummingbird functional diversity. For a subset of 28 networks, we additionally evaluated whether plant functional diversity was associated with hummingbird functional diversity and network structure. Results Precipitation, insularity and plant richness, together with hummingbird functional diversity (specifically, functional dispersion), were consistently strong predictors of niche partitioning in plant–hummingbird networks. Moreover, SEMs showed that environmental predictors and plant richness affected network structure both directly and indirectly through their effects on hummingbird functional diversity. Plant functional diversity, however, was unrelated to hummingbird functional diversity and network structure. Main conclusions: We reveal the importance of hummingbird functional diversity for niche partitioning in plant–hummingbird interaction networks. The lack of support for similar effects for plant functional diversity potentially indicates that consumer functional diversity might be more important for structuring interaction networks than resource functional diversity. Changes in pollinator functional diversity are therefore likely to alter the structure of interaction networks and associated ecosystem functions.

Linking Capacity Development to GOOS Monitoring Networks to Achieve Sustained Ocean Observation - Nicholas J. Bax; Ward Appeltans; Russell Brainard; J. Emmett Duffy; Piers Dunstan; Quentin Hanich; Harriet Harden Davies; Jeremy Hills; Patricia Miloslavich; Frank Edgar Muller-Karger; Samantha Simmons; O. Aburto-Oropeza; et al. (Frontiers in Marine Science, 2018)

Technologies and logistics for phosphorus recovery from livestock waste - Apoorva M. Sampat; Edgar Martín-Hernández; Mariano Martín; Victor M. Zavala (Clean Technologies and Environmental Policy, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Logging disturbance shifts net primary productivity and its allocation in Bornean tropical forests - Terhi Riutta; Yadvinder Malhi; Lip Khoon Kho; Toby R. Marthews; Walter Huaraca Huasco; MinSheng Khoo; Sylvester Tan; Edgar Turner; Glen Reynolds; Sabine Both; David F.R.P. Burslem; Yit Arn Teh; et al. (Global Change Biology, 2018)
Tropical forests play a major role in the carbon cycle of the terrestrial biosphere. Recent field studies have provided detailed descriptions of the carbon cycle of mature tropical forests, but logged or secondary forests have received much less attention. Here, we report the first measures of total net primary productivity ( NPP ) and its allocation along a disturbance gradient from old‐growth forests to moderately and heavily logged forests in Malaysian Borneo. We measured the main NPP components (woody, fine root and canopy NPP ) in old‐growth ( n = 6) and logged ( n = 5) 1 ha forest plots. Overall, the total NPP did not differ between old‐growth and logged forest (13.5 ± 0.5 and 15.7 ± 1.5 Mg C ha −1 year −1 respectively). However, logged forests allocated significantly higher fraction into woody NPP at the expense of the canopy NPP (42% and 48% into woody and canopy NPP , respectively, in old‐growth forest vs 66% and 23% in logged forest). When controlling for local stand structure, NPP in logged forest stands was 41% higher, and woody NPP was 150% higher than in old‐growth stands with similar basal area, but this was offset by structure effects (higher gap frequency and absence of large trees in logged forest). This pattern was not driven by species turnover: the average woody NPP of all species groups within logged forest (pioneers, nonpioneers, species unique to logged plots and species shared with old‐growth plots) was similar. Hence, below a threshold of very heavy disturbance, logged forests can exhibit higher NPP and higher allocation to wood; such shifts in carbon cycling persist for decades after the logging event. Given that the majority of tropical forest biome has experienced some degree of logging, our results demonstrate that logging can cause substantial shifts in carbon production and allocation in tropical forests.

Differential recognition of natural and remodeled glycotopes by three Diocleae lectins - Tania M. Cortázar; Iain B. H. Wilson; Alba Hykollari; Edgar A. Reyes; Nohora A. Vega (Glycoconjugate Journal, 2018)

Dissecting the Effects of Diameter on Wood Decay Emphasizes the Importance of Cross-Stem Conductivity in Fraxinus americana - Brad Oberle; Kristofer R. Covey; Kevin M. Dunham; Edgar J. Hernandez; Maranda L. Walton; Darcy F. Young; Amy E. Zanne (Ecosystems, 2018)

Mass and energy allocation method analysis for an oil refinery characterization using multi-scale modeling - Edgar A. Silveira; Armando Caldeira-Pires; Sandra M. Luz; Cristiano M. Silveira (The International Journal of Life Cycle Assessment, 2017)

Chemical constituents and antileukemic activity of Eugenia dysenterica - Renan Vitek; Leice M. R. de Novais; Heron F. V. Torquato; Edgar J. Paredes-Gamero; Mário G. de Carvalho; Paulo T. de Sousa; Marcos J. Jacinto; Virgínia C. da Silva (Natural Product Research, 2017)

Long-Term Release of Carbon Dioxide from Arctic Tundra Ecosystems in Alaska - E. S. Euskirchen; M. S. Bret-Harte; G. R. Shaver; C. W. Edgar; V. E. Romanovsky (Ecosystems, 2017)

White matter hyperintensities correlate to cognition and fiber tract integrity in older adults with HIV - Christa Watson; Edgar Busovaca; Jessica M. Foley; I. Elaine Allen; Christopher G. Schwarz; Neda Jahanshad; Talia M. Nir; Pardis Esmaeili-Firidouni; Benedetta Milanini; Howard Rosen; Owen T. Carmichael; Paul M. Thompson; et al. (Journal of NeuroVirology, 2017)

Genetic Variants of Microtubule Actin Cross-linking Factor 1 (MACF1) Confer Risk for Parkinson’s Disease - Xin Wang; Nuomin Li; Nian Xiong; Qi You; Jie Li; Jinlong Yu; Hong Qing; Tao Wang; Heather J. Cordell; Ole Isacson; Jeffery M. Vance; Eden R. Martin; et al. (Molecular Neurobiology, 2017)

Canine distemper virus in the Serengeti ecosystem: molecular adaptation to different carnivore species - Veljko M. Nikolin; Ximena A. Olarte‐Castillo; Nikolaus Osterrieder; Heribert Hofer; Edward Dubovi; Camila J. Mazzoni; Edgar Brunner; Katja V. Goller; Robert D. Fyumagwa; Patricia D. Moehlman; Dagmar Thierer; Marion L. East (Molecular Ecology, 2017)
Was the 1993/1994 fatal canine distemper virus ( CDV ) epidemic in lions and spotted hyaenas in the Serengeti ecosystem caused by the recent spillover of a virulent domestic dog strain or one well adapted to these noncanids? We examine this question using sequence data from 13 ‘Serengeti’ strains including five complete genomes obtained between 1993 and 2011. Phylogenetic and haplotype network analyses reveal that strains from noncanids during the epidemic were more closely related to each other than to those from domestic or wild canids. All noncanid ‘Serengeti’ strains during the epidemic encoded: (1) one novel substitution G134S in the CDV ‐V protein; and (2) the rare amino acid combination 519I/549H at two sites under positive selection in the region of the CDV ‐H protein that binds to SLAM ( CD 150) host cell receptors. Worldwide, only a few noncanid strains in the America II lineage encode CDV ‐H 519I/549H. All canid ‘Serengeti’ strains during the epidemic coded CDV ‐V 134G, and CDV ‐H 519R/549Y, or 519R/549H. A functional assay of cell entry revealed the highest performance by CDV ‐H proteins encoding 519I/549H in cells expressing lion SLAM receptors, and the highest performance by proteins encoding 519R/549Y, typical of dog strains worldwide, in cells expressing dog SLAM receptors. Our findings are consistent with an epidemic in lions and hyaenas caused by CDV variants better adapted to noncanids than canids, but not with the recent spillover of a dog strain. Our study reveals a greater complexity of CDV molecular epidemiology in multihost environments than previously thought.

Heavy metals and pesticide exposure from agricultural activities and former agrochemical factory in a Salvadoran rural community - Edgar Quinteros; Alexandre Ribó; Roberto Mejía; Alejandro López; Wilfredo Belteton; Aimee Comandari; Carlos M. Orantes; Ernesto B. Pleites; Carlos E. Hernández; Dina L. López (Environmental Science and Pollution Research, 2017)

Effects of Chrysosporum (Aphanizomenon) ovalisporum extracts containing cylindrospermopsin on growth, photosynthetic capacity, and mineral content of carrots (Daucus carota) - Remedios Guzmán-Guillén; Alexandre Campos; Joana Machado; Marisa Freitas; Joana Azevedo; Edgar Pinto; Agostinho Almeida; Ana M. Cameán; Vitor Vasconcelos (Ecotoxicology, 2017)

Tracing seaweeds as mineral sources for farm-animals - Ana R. J. Cabrita; Margarida R. G. Maia; Hugo M. Oliveira; Isabel Sousa-Pinto; Agostinho A. Almeida; Edgar Pinto; António J. M. Fonseca (Journal of Applied Phycology, 2016)

A saturated SNP linkage map for the orange wheat blossom midge resistance gene Sm1 - Mulualem T. Kassa; Sabrina Haas; Edgar Schliephake; Clare Lewis; Frank M. You; Curtis J. Pozniak; Ilona Krämer; Dragan Perovic; Andrew G. Sharpe; Pierre R. Fobert; Michael Koch; Ian L. Wise; et al. (Theoretical and Applied Genetics, 2016)

Is the Alzheimer’s disease cortical thickness signature a biological marker for memory? - Edgar Busovaca; Molly E. Zimmerman; Irene B. Meier; Erica Y. Griffith; Stuart M. Grieve; Mayuresh S. Korgaonkar; Leanne M. Williams; Adam M. Brickman (Brain Imaging and Behavior, 2016)

Molecular characterization of infectious bursal disease viruses detected in vaccinated commercial broiler flocks in Lusaka, Zambia - Kunda Ndashe; Edgar Simulundu; Bernard M Hang’ombe; Ladslav Moonga; Hirohito Ogawa; Ayato Takada; Aaron S Mweene (Archives of Virology, 2016)

Intrinsic network connectivity abnormalities in HIV-infected individuals over age 60 - Anika Guha; Liang Wang; Aaron Tanenbaum; Pardis Esmaeili-Firidouni; Lauren A. Wendelken; Edgar Busovaca; Katherine Clifford; Akash Desai; Beau M. Ances; Victor Valcour (Journal of NeuroVirology, 2016)

Distinct pro-vigilant profile induced in rats by the mGluR5 potentiator LSN2814617 - Sally Loomis; Andrew McCarthy; Christopher Baxter; Daniel O. Kellett; Dale M. Edgar; Mark Tricklebank; Gary Gilmour (Psychopharmacology, 2015)

Species traits and climate velocity explain geographic range shifts in an ocean‐warming hotspot - Jennifer M. Sunday; Gretta T. Pecl; Stewart Frusher; Alistair J. Hobday; Nicole Hill; Neil J. Holbrook; Graham J. Edgar; Rick Stuart‐Smith; Neville Barrett; Thomas Wernberg; Reg A. Watson; Dan A. Smale; et al. (Ecology Letters, 2015)
Species' ranges are shifting globally in response to climate warming, with substantial variability among taxa, even within regions. Relationships between range dynamics and intrinsic species traits may be particularly apparent in the ocean, where temperature more directly shapes species' distributions. Here, we test for a role of species traits and climate velocity in driving range extensions in the ocean‐warming hotspot of southeast Australia. Climate velocity explained some variation in range shifts, however, including species traits more than doubled the variation explained. Swimming ability, omnivory and latitudinal range size all had positive relationships with range extension rate, supporting hypotheses that increased dispersal capacity and ecological generalism promote extensions. We find independent support for the hypothesis that species with narrow latitudinal ranges are limited by factors other than climate. Our findings suggest that small‐ranging species are in double jeopardy, with limited ability to escape warming and greater intrinsic vulnerability to stochastic disturbances.

An ant–plant by-product mutualism is robust to selective logging of rain forest and conversion to oil palm plantation - Tom M. Fayle; David P. Edwards; William A. Foster; Kalsum M. Yusah; Edgar C. Turner (Oecologia, 2015)

Testosterone-induced relaxation involves L-type and store-operated Ca2+ channels blockade, and PGE2 in guinea pig airway smooth muscle - Mercedes Perusquía; Edgar Flores-Soto; Bettina Sommer; Elias Campuzano-González; Inocencio Martínez-Villa; Aldo I. Martínez-Banderas; Luis M. Montaño (Pflügers Archiv - European Journal of Physiology, 2015)

Association between brain volumes and HAND in cART-naïve HIV+ individuals from Thailand - Jodi M. Heaps; Pasiri Sithinamsuwan; Robert Paul; Sukalaya Lerdlum; Mantana Pothisri; David Clifford; Somporn Tipsuk; Stephanie Catella; Edgar Busovaca; James L. K. Fletcher; Benjamin Raudabaugh; Silvia Ratto-Kim; et al. (Journal of NeuroVirology, 2015)

Multi-environment multi-QTL association mapping identifies disease resistance QTL in barley germplasm from Latin America - Lucia Gutiérrez; Silvia Germán; Silvia Pereyra; Patrick M. Hayes; Carlos A. Pérez; Flavio Capettini; Andres Locatelli; Natalia M. Berberian; Esteban E. Falconi; Rigoberto Estrada; Dario Fros; Victor Gonza; et al. (Theoretical and Applied Genetics, 2015)

Preclinical Pharmacokinetic/Pharmacodynamic Modeling and Simulation in the Pharmaceutical Industry: An IQ Consortium Survey Examining the Current Landscape - Edgar Schuck; Tonika Bohnert; Arijit Chakravarty; Valeriu Damian-Iordache; Christopher Gibson; Cheng-Pang Hsu; Tycho Heimbach; Anu Shilpa Krishnatry; Bianca M Liederer; Jing Lin; Tristan Maurer; Jerome T Mettetal; et al. (The AAPS Journal, 2015)

Roles of bacterial membrane vesicles - Eric Daniel Avila-Calderón; Minerva Georgina Araiza-Villanueva; Juan Carlos Cancino-Diaz; Edgar Oliver López-Villegas; Nammalwar Sriranganathan; Stephen M. Boyle; Araceli Contreras-Rodríguez (Archives of Microbiology, 2015)

Over 75 years of zooplankton data from Australia - Claire H. Davies; Amelia J. Armstrong; Mark Baird; Frank Coman; Steven Edgar; Daniel Gaughan; Jack Greenwood; Felipe Gusmão; Natasha Henschke; J. Anthony Koslow; Sophie C. Leterme; A. David McKinnon; et al. (Ecology, 2014)
Zooplankton are the key trophic link between primary producers and fish in pelagic ecosystems. Historically, there are few zooplankton time series in Australia, with no data sets longer than two years prior to 2008. Here we compile 98 676 abundance records of more than 1000 zooplankton taxa from unpublished research cruises, student projects, published literature, and the recent Integrated Marine Observing System (IMOS). This data set covers the entire coastal and shelf region of Australia and dates back to 1938. Most records are for copepods, but there are also data for other taxa such as decapods, chaetognaths, thaliaceans, appendicularians, and cladocerans. Metadata are provided for each record, including dates, coordinates, and information on mesh size and sampling methods. To facilitate analysis across the multiple data sets, we have updated the species names according to the World Register of Marine Species (WoRMS) and converted units to abundance per cubic meter. These data will be valuable for studies of biodiversity, biogeography, impacts of climate change, and ecosystem health. We encourage researchers holding additional Australian zooplankton data to contact us and contribute their data to the data set so we can periodically publish updates.

Effects of high glucose and high insulin concentrations on osteoblast function in vitro - Juliana S. Cunha; Vanessa M. Ferreira; Edgar Maquigussa; Marcelo A. Naves; Mirian A. Boim (Cell and Tissue Research, 2014)

Functional structure of ant and termite assemblages in old growth forest, logged forest and oil palm plantation in Malaysian Borneo - Sarah H. Luke; Tom M. Fayle; Paul Eggleton; Edgar C. Turner; Richard G. Davies (Biodiversity and Conservation, 2014)

Improved allometric models to estimate the aboveground biomass of tropical trees - Jérôme Chave; Maxime Réjou‐Méchain; Alberto Búrquez; Emmanuel Chidumayo; Matthew S. Colgan; Welington B.C. Delitti; Alvaro Duque; Tron Eid; Philip M. Fearnside; Rosa C. Goodman; Matieu Henry; Angelina Martínez‐Yrízar; et al. (Global Change Biology, 2014)
Terrestrial carbon stock mapping is important for the successful implementation of climate change mitigation policies. Its accuracy depends on the availability of reliable allometric models to infer oven‐dry aboveground biomass of trees from census data. The degree of uncertainty associated with previously published pantropical aboveground biomass allometries is large. We analyzed a global database of directly harvested trees at 58 sites, spanning a wide range of climatic conditions and vegetation types (4004 trees ≥ 5 cm trunk diameter). When trunk diameter, total tree height, and wood specific gravity were included in the aboveground biomass model as covariates, a single model was found to hold across tropical vegetation types, with no detectable effect of region or environmental factors. The mean percent bias and variance of this model was only slightly higher than that of locally fitted models. Wood specific gravity was an important predictor of aboveground biomass, especially when including a much broader range of vegetation types than previous studies. The generic tree diameter–height relationship depended linearly on a bioclimatic stress variable E , which compounds indices of temperature variability, precipitation variability, and drought intensity. For cases in which total tree height is unavailable for aboveground biomass estimation, a pantropical model incorporating wood density, trunk diameter, and the variable E outperformed previously published models without height. However, to minimize bias, the development of locally derived diameter–height relationships is advised whenever possible. Both new allometric models should contribute to improve the accuracy of biomass assessment protocols in tropical vegetation types, and to advancing our understanding of architectural and evolutionary constraints on woody plant development.

Influence of mixtures of acenaphthylene and benzo[a]anthracene on their degradation by Pleurotus ostreatus in sandy soil - Inês Rocha; Edgar Pinto; Isabel M. P. L. V. O. Ferreira; Manuela V. da Silva; Rui S. Oliveira (Journal of Soils and Sediments, 2014)

Kinin B1 receptor deficiency attenuates cisplatin-induced acute kidney injury by modulating immune cell migration - Gabriel R. Estrela; Frederick Wasinski; Danilo C. Almeida; Mariane T. Amano; Angela Castoldi; Carolina C. Dias; Denise M. A. C. Malheiros; Sandro S. Almeida; Edgar J. Paredes-Gamero; João B. Pesquero; Carlos C. Barros; Niels O. S. Câmara; et al. (Journal of Molecular Medicine, 2014)

Implications of Macroalgal Isolation by Distance for Networks of Marine Protected Areas - HALLEY M. S. DURRANT; CHRISTOPHER P. BURRIDGE; BRENDAN P. KELAHER; NEVILLE S. BARRETT; GRAHAM J. EDGAR; MELINDA A. COLEMAN (Conservation Biology, 2014)
The global extent of macroalgal forests is declining, greatly affecting marine biodiversity at broad scales through the effects macroalgae have on ecosystem processes, habitat provision, and food web support. Networks of marine protected areas comprise one potential tool that may safeguard gene flow among macroalgal populations in the face of increasing population fragmentation caused by pollution, habitat modification, climate change, algal harvesting, trophic cascades, and other anthropogenic stressors. Optimal design of protected area networks requires knowledge of effective dispersal distances for a range of macroalgae. We conducted a global meta‐analysis based on data in the published literature to determine the generality of relation between genetic differentiation and geographic distance among macroalgal populations. We also examined whether spatial genetic variation differed significantly with respect to higher taxon, life history, and habitat characteristics. We found clear evidence of population isolation by distance across a multitude of macroalgal species. Genetic and geographic distance were positively correlated across 49 studies; a modal distance of 50–100 km maintained F ST Implicaciones del Aislamiento por Distancia de Macroalgas para Redes de Áreas Marinas Protegidas

Analysis of heat-labile sites generated by reactions of depleted uranium and ascorbate in plasmid DNA - Janice Wilson; Ashley Young; Edgar R. Civitello; Diane M. Stearns (JBIC Journal of Biological Inorganic Chemistry, 2014)

Identifying Risk Factors for HIV-Associated Neurocognitive Disorders Using the International HIV Dementia Scale - Sara Cross; Nur Önen; Amber Gase; Edgar Turner Overton; Beau M. Ances (Journal of Neuroimmune Pharmacology, 2013)

The genus Pseudo‐nitzschia (Bacillariophyceae) in New Zealand: analysis of the last decade's monitoring data - L Rhodes; W Jiang; B Knight; J Adamson; K Smith; V Langi; M Edgar (New Zealand Journal of Marine and Freshwater Research, 2013)
The diatom genus Pseudo‐nitzschia blooms throughout New Zealand's coastal waters. More than a decade of monitoring data were analysed in this study and seasonality was a significant factor in the appearance of Pseudo‐nitzschia blooms. Austral spring and summer were the main bloom periods, although there were regional differences. Between January 2000 and August 2011, 8.4% of 29,000 seawater samples analysed for Pseudo‐nitzschia exceeded the voluntary trigger level for biotoxin testing (10×10 4 cells l −1 ), and these were analysed by fluorescent in situ hybridisation (FISH) assays. Pseudo‐nitzschia fraudulenta and P. pseudodelicatissima (low domoic acid [DA] producers) were the dominant bloom formers throughout New Zealand (each contributing 25%) followed by the highly toxic P. australis (10%). Shellfish flesh testing for DA was triggered on 8477 occasions between 2000 and 2011, but no samples exceeded the regulatory limit (20 mg/kg); the maximum concentration was 13 mg/kg (Marlborough Sounds, mid‐winter 2010).

Assessment of novel binocular colour, motion and contrast tests in glaucoma - Franziska G. Rauscher; Catharine M. Chisholm; David F. Edgar; John L. Barbur (Cell and Tissue Research, 2013)

Characterization of the GGPP synthase gene family in Arabidopsis thaliana - Gilles Beck; Diana Coman; Edgar Herren; M. Águila Ruiz-Sola; Manuel Rodríguez-Concepción; Wilhelm Gruissem; Eva Vranová (Plant Molecular Biology, 2013)

Development and characterization of an exposure generation system to investigate the health effects of particles from fresh and aged traffic emissions - Vasileios Papapostolou; Joy E. Lawrence; Stephen T. Ferguson; Jack M. Wolfson; Edgar A. Diaz; John J. Godleski; Petros Koutrakis (Air Quality, Atmosphere & Health, 2013)

Protein Phosphatase 1γ Isoforms Linked Interactions in the Brain - Sara L. C. Esteves; Luís Korrodi-Gregório; Cândida Z. Cotrim; Paula J. M. van Kleeff; Sara C. Domingues; Odete A. B. da Cruz e Silva; Margarida Fardilha; Edgar F. da Cruz e Silva (Journal of Molecular Neuroscience, 2013)

The Alzheimer’s disease-8 and Montreal Cognitive Assessment as screening tools for neurocognitive impairment in HIV-infected persons - Edgar Turner Overton; Tej D. Azad; Neva Parker; Debra Demarco Shaw; Judy Frain; Teresa Spitz; Elizabeth Westerhaus; Robert Paul; David B. Clifford; Beau M. Ances (Journal of NeuroVirology, 2013)

Impact of intensive horticulture practices on groundwater content of nitrates, sodium, potassium, and pesticides - Armindo Melo; Edgar Pinto; Ana Aguiar; Catarina Mansilha; Olívia Pinho; Isabel M. P. L. V. O. Ferreira (Environmental Monitoring and Assessment, 2012)

Bacteremic complications of intravascular catheter tip colonization with Gram-negative micro-organisms in patients without preceding bacteremia - A. van Eck van der Sluijs; J. J. Oosterheert; M. B. Ekkelenkamp; I. M. Hoepelman; Edgar J. G. Peters (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Diversification of hAT transposase paralogues in the sugarcane genome - Erika M. de Jesus; Edgar A. Ochoa Cruz; Guilherme M. Q. Cruz; Marie-Anne Van Sluys (Molecular Genetics and Genomics, 2012)

The Relationship Between Subconcussive Impacts and Concussion History on Clinical Measures of Neurologic Function in Collegiate Football Players - Sonia M. Gysland; Jason P. Mihalik; Johna K. Register-Mihalik; Scott C. Trulock; Edgar W. Shields; Kevin M. Guskiewicz (Annals of Biomedical Engineering, 2012)

New records of Staurozoa from Australian coastal waters, with a description of a new species of Lucernariopsis Uchida, 1929 (Cnidaria, Staurozoa, Stauromedusae) and a key to Australian Stauromedusae - Carolina J. Zagal; Yayoi M. Hirano; Claudia E. Mills; Graham J. Edgar; Neville S. Barrett (Marine Biology Research, 2011)

Characterization of P2Y receptors mediating ATP induced relaxation in guinea pig airway smooth muscle: involvement of prostaglandins and K+ channels - Luis M. Montaño; José E. Cruz-Valderrama; Alejandra Figueroa; Edgar Flores-Soto; Luz M. García-Hernández; Verónica Carbajal; Patricia Segura; Carmen Méndez; Verónica Díaz; Carlos Barajas-López (Pflügers Archiv - European Journal of Physiology, 2011)

Reconstructing the Fungal Tree of Life Using Phylogenomics and a Preliminary Investigation of the Distribution of Yeast Prion-Like Proteins in the Fungal Kingdom - Edgar M. Medina; Gary W. Jones; David A. Fitzpatrick (Journal of Molecular Evolution, 2011)

Photogrammetric and spatial analysis of a bioeroded Early Miocene rocky shore, western Portugal - Mário Cachão; Paula Redweik; Edgar Barreira; Joel Dinis; Cristina Catita; Carlos M. da Silva; Ana Santos; Eduardo Mayoral; Wilfried Linder (Facies, 2011)

Pyrrolizidine alkaloids in food: a spectrum of potential health consequences - J.A. Edgar; S.M. Colegate; M. Boppré; R.J. Molyneux (Food Additives & Contaminants: Part A, 2011)

In airways ATP refills sarcoplasmic reticulum via P2X smooth muscle receptors and induces contraction through P2Y epithelial receptors - Edgar Flores-Soto; Verónica Carbajal; Jorge Reyes-García; Luz María García-Hernández; Alejandra Figueroa; Marco Checa; Carlos Barajas-López; Luis M. Montaño (Pflügers Archiv - European Journal of Physiology, 2011)

Mutation analysis in Bardet–Biedl syndrome by DNA pooling and massively parallel resequencing in 105 individuals - Sabine Janssen; Gokul Ramaswami; Erica E. Davis; Toby Hurd; Rannar Airik; Jennifer M. Kasanuki; Lauren Van Der Kraak; Susan J. Allen; Philip L. Beales; Nicholas Katsanis; Edgar A. Otto; Friedhelm Hildebrandt (Human Genetics, 2011)

El Niño, grazers and fisheries interact to greatly elevate extinction risk for Galapagos marine species - GRAHAM J. EDGAR; STUART A. BANKS; MARGARITA BRANDT; RODRIGO H. BUSTAMANTE; ANGEL CHIRIBOGA; SYLVIA A. EARLE; LAUREN E. GARSKE; PETER W. GLYNN; JACK S. GROVE; SCOTT HENDERSON; CLEVE P. HICKMAN; KATHY A. MILLER; et al. (Global Change Biology, 2010)
Comparisons between historical and recent ecological datasets indicate that shallow reef habitats across the central Galapagos Archipelago underwent major transformation at the time of the severe 1982/1983 El Niño warming event. Heavily grazed reefs with crustose coralline algae (‘urchin barrens’) replaced former macroalgal and coral habitats, resulting in large local and regional declines in biodiversity. Following recent threat assessment workshops, a total of five mammals, six birds, five reptiles, six fishes, one echinoderm, seven corals, six brown algae and nine red algae reported from coastal environments in Galapagos are now recognized as globally threatened. The 2008 International Union for the Conservation of Nature (IUCN) Red List includes 43 of these species, while two additional species (Galapagos damsel Azurina eupalama and 24‐rayed sunstar Heliaster solaris ) not seen for > 25 years also fulfil IUCN threatened species criteria. Two endemic species (Galapagos stringweed Bifurcaria galapagensis and the damselfish A. eupalama ) are now regarded as probably extinct, while an additional six macroalgal species ( Dictyota galapagensis, Spatoglossum schmittii, Desmarestia tropica, Phycodrina elegans, Gracilaria skottsbergii and Galaxaura barbata ) and the seastar H. solaris are possibly extinct. The removal of large lobster and fish predators by artisanal fishing probably magnified impacts of the 1982/1983 El Niño through a cascade of indirect effects involving population expansion of grazing sea urchins. Marine protected areas with adequate enforcement are predicted to ameliorate but not eliminate ecosystem impacts caused by increasing thermal anomalies associated with El Niño and global climate change.

The Biotechnology Roadmap for Sugarcane Improvement - Carlos T. Hotta; Carolina G. Lembke; Douglas S. Domingues; Edgar A. Ochoa; Guilherme M. Q. Cruz; Danila M. Melotto-Passarin; Thiago G. Marconi; Melissa O. Santos; Marcelo Mollinari; Gabriel R. A. Margarido; Augusto César Crivellari; Wanderley D. dos Santos; et al. (Tropical Plant Biology, 2010)

Propafenone Poisoning—A Case Report with Plasma Propafenone Concentrations - Hanna Ovaska; Andrew Ludman; Edgar P. Spencer; David M. Wood; Alison L. Jones; Paul I. Dargan (Journal of Medical Toxicology, 2010)

Somatosensory System Deficits in Schizophrenia Revealed by MEG during a Median-Nerve Oddball Task - Ming-Xiong Huang; Roland R. Lee; Kathleen M. Gaa; Tao Song; Deborah L. Harrington; Cathy Loh; Rebecca J. Theilmann; J. Christopher Edgar; Gregory A. Miller; Jose M. Canive; Eric Granholm (Brain Topography, 2010)

Habitat preference and dispersal of the Duke of Burgundy butterfly (Hamearis lucina) on an abandoned chalk quarry in Bedfordshire, UK - Edgar C. Turner; Hanna M. V. Granroth; Henry R. Johnson; Colin B. H. Lucas; Alex M. Thompson; Hannah Froy; Richard N. German; Ross Holdgate (Journal of Insect Conservation, 2009)

Revision of the amphiamerican Neotetraonchus Bravo-Hollis, 1968 (Monogenoidea: Dactylogyridae), with a description of N. vegrandis n. sp. from the gill lamellae of the blue sea catfish Ariopsis guatemalensis (Siluriformes: Ariidae) off the Pacific Coast of Mexico - Delane C. Kritsky; Edgar F. Mendoza-Franco; Stephen A. Bullard; Victor M. Vidal-Martínez (Systematic Parasitology, 2009)

Characterization of H3N6 avian influenza virus isolated from a wild white pelican in Zambia - Edgar Simulundu; Aaron S. Mweene; Daisuke Tomabechi; Bernard M. Hang’ombe; Akihiro Ishii; Yuka Suzuki; Ichiro Nakamura; Hirofumi Sawa; Chihiro Sugimoto; Kimihito Ito; Hiroshi Kida; Lewis Saiwana; et al. (Archives of Virology, 2009)

Impact of moisture dynamic and sun light on anthracene removal from soil - Edgar Vázquez Núñez; Alejandro García Gaytán; M. Luna-Guido; R. Marsch; L. Dendooven (Biodegradation, 2009)

Anticholinergic antiparkinson drug orphenadrine inhibits HERG channels: block attenuation by mutations of the pore residues Y652 or F656 - Eberhard P. Scholz; Franziska M. Konrad; Daniel L. Weiss; Edgar Zitron; Claudia Kiesecker; Ramona Bloehs; Martin Kulzer; Dierk Thomas; Sven Kathöfer; Alexander Bauer; Martin H. Maurer; Gunnar Seemann; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2007)

Regeneration patterns of Polylepis subtusalbida growing with the exotic trees Pinus radiata and Eucalyptus globulus at Parque Nacional Tunari, Bolivia - Edgar E. Gareca; Yvonne Y. Martinez; Ramiro O. Bustamante; Luis F. Aguirre; Melicio M. Siles (Plant Ecology, 2007)

Isolation and characterization of the potential receptor for wheat germ agglutinin from human neutrophils - Carlos Solórzano; Stéphane Bouquelet; M. Ali Pereyra; Francisco Blanco-Favela; Marie-Christine Slomianny; Raúl Chavez; Ricardo Lascurain; Edgar Zenteno; Concepción Agundis (Glycoconjugate Journal, 2006)

Medullary cystic kidney disease type 1: mutational analysis in 37 genes based on haplotype sharing - Matthias T. F. Wolf; Bettina E. Mucha; Hans C. Hennies; Massimo Attanasio; Franziska Panther; Isabella Zalewski; Stephanie M. Karle; Edgar A. Otto; C. Constantinou Deltas; Arno Fuchshuber; Friedhelm Hildebrandt (Human Genetics, 2006)

Monogeneans on native and introduced freshwater fishes from Cuba with the description of a new species of Salsuginus Beverley-Burton, 1984 from Limia vittata (Poeciliidae) - Edgar F. Mendoza-Franco; V. M. Vidal-Martínez; Y. Cruz-Quintana; F. L. Prats León (Systematic Parasitology, 2006)

Regulation of cardiac inwardly rectifying potassium current IK1 and Kir2.x channels by endothelin-1 - Claudia Kiesecker; Edgar Zitron; Daniel Scherer; Sonja Lueck; Ramona Bloehs; Eberhard P. Scholz; Marcus Pirot; Sven Kathöfer; Dierk Thomas; Volker A. W. Kreye; Johann Kiehn; Mathias M. Borst; et al. (Journal of Molecular Medicine, 2006)

Salicylic acid mediates resistance to the vascular wilt pathogen Fusarium oxysporum in the model host Arabidopsis thaliana - C. I. Edgar; K. C. McGrath; B. Dombrecht; J. M. Manners; D. C. Maclean; P. M. Schenk; K. Kazan (Australasian Plant Pathology, 2006)

Regional biogeography of shallow reef fish and macro‐invertebrate communities in the Galapagos archipelago - G. J. Edgar; S. Banks; J. M. Fariña; M. Calvopiña; C. Martínez (Journal of Biogeography, 2004)
Aim To delineate biogeographical patterns in Galapagos shallow‐water reef fauna at regional scales. Location Galapagos Islands. Methods Fishes and macro‐invertebrates were quantitatively censused using underwater visual techniques along more than 500 transects at defined depth strata across the Galapagos archipelago. Data were analysed using multivariate techniques to define regional patterns and identify species typical of different regions. Results Subtidal communities of fishes and macro‐invertebrates on shallow reefs differed consistently in species composition across the Galapagos archipelago, with three major biogeographical groupings: (1) the ‘far‐northern area’ containing the islands of Darwin and Wolf, (2) the ‘central/south‐eastern area’, including the east coast of Isabela, and (3) the ‘western area’, encompassing Fernandina and western Isabela. In addition, the northern islands of Pinta, Marchena and Genovesa form a separate region in the central/south‐eastern area, and Bahia Elizabeth and Canal Bolivar separate from other parts of the western area. The far‐northern bioregion is characterized by high fish species richness overall, including a high proportion of species of Indo‐Pacific origin. However, very few endemic fishes or species with distributions extending south from Ecuador (‘Peruvian’ species) are present, and the bioregion also possesses relatively low species richness of mobile macro‐invertebrate taxa. By contrast, the ‘western’ bioregion possesses disproportionately high numbers of endemic fish taxa, high numbers of cool‐temperate Peruvian fish species, and high invertebrate species richness, but very few species of Indo‐Pacific origin. The Bahia Elizabeth/Canal Bolivar bioregion possesses more endemic species and fewer species with Peruvian affinities than coasts within the western bioregion. The northern bioregion of Pinta, Marchena and Genovesa represents an overlap zone with affinities to both the far‐northern and south‐eastern islands. The south‐eastern bioregion includes species from a variety of different sources, particularly ‘Panamic’ species with distributions extending north to Central America. Main conclusions On the basis of congruent divisions for reef fish and macro‐invertebrate communities, the Galapagos archipelago can be separated into three major biogeographical areas, two of which can be further subdivided into two regions. Each of these five bioregions possesses communities characterized by a distinctive mix of species derived from Indo‐Pacific, Panamic, Peruvian and endemic source areas. The conservation significance of different regions is not reflected in counts of total species richness. The regions with the lowest overall fish species richness possess a temperate rather than tropical climate and highest levels of endemism.

Role of sarcoplasmic reticulum Ca 2+ content in Ca 2+ entry of bovine airway smooth muscle cells - Blanca Bazn-Perkins; Edgar Flores-Soto; Carlos Barajas-Lpez; Luis M. Montao (Naunyn-Schmiedeberg's Archives of Pharmacology, 2003)

Increase in the indole alkaloid production and its excretion into the culture medium by calcium antagonists inCatharanthus roseus hairy roots - Oscar A. Moreno-Valenzuela; Yereni Minero-García; Wilson Chan; Edgar Mayer-Geraldo; Eloisa Carbajal; Víctor M. Loyola-Vargas (Biotechnology Letters, 2003)

Development and preliminary clinical tests of an impedance sensing VDD recording pacemaker for diagnosis and research - D. R. Edgar; J. M. K. Horwood; D. J. Woollons; J. Baker; D. B. Shaw (Medical & Biological Engineering & Computing, 1999)

Actin expression in germinating seeds of Phaseolus vulgaris L. - Marco A. Villanueva; Francisco Campos; Claudia Díaz; José M. Colmenero-Flores; Edgar Dantán; Federico Sánchez; Alejandra A. Covarrubias (Planta, 1999)

Loss of cell surface microvilli on rat basophilic leukaemia cells precedes secretion and can be mimicked using the calmodulin antagonist trifluoperazine - A. J. Edgar; G. R. Davies; M. A. Anwar; J. P. Bennett (Inflammation Research, 1997)

Comparative genomic hybridization reveals a partial de novo trisomy 6q23-qter in an infant with congenital malformations: delineation of the phenotype - M. Erdel; Hans-Christoph Duba; Irmgard Verdorfer; Arno Lingenhel; Ralf Geiger; Karl-Heinz Gutenberger; Edgar Ludescher; Barbara Utermann; Gerd Utermann (Human Genetics, 1997)

Depression of the synthesis of the intermediate and large forms of ribulose-1,5-bisphosphate carboxylase/oxygenase in Rhodopseudomonas capsulata - Jessup M. Shively; Edgar Davidson; Barry L. Marrs (Archives of Microbiology, 1984)

Reducing injuries in grading stored potatoes - J. M. Lutz; A. D. Edgar; A. H. Glaves (American Journal of Potato Research, 1952)

Research on harvesting, transportation and storage of potatoes—A review of recent literature - J. M. Lutz; R. C. Wright; A. D. Edgar (American Journal of Potato Research, 1948)